Amphiphilic polyester-b-poly (vinyl amide) copolymers as dual functional kinetic hydrate inhibitors and anti-agglomerants for multiphase flow-assurance - Xiang-Long Ding; Hong-Ju Huang; Yi-Min Dai; Li Wan (Fuel, 2027)

Contrasting land uses mediate divergent N2O uptake through nosZ clade II and carbon availability: Evidence from 15N2O pool dilution in black soils - Hongshan Liu; Xiangzhou Zheng; Baobao Pan; Hong Ding; Yuefen Li; Yushu Zhang (Soil Ecology Letters, 2026)

Current Advances in Microbial Degradation for Fluoroquinolones: Degraders, Mechanisms and Applications - Tongtong Liu; Qin Ding; Yuan Hong; Zhuoxiao Li; Rongli Sun; Juan Zhang (Reviews of Environmental Contamination and Toxicology, 2026)

Effects of different function-oriented hydrochars on anaerobic digestion of hydrothermal wastewater: Focusing on microbial community function and organic degradation - Hong Zhang; Gengxin Xie; Li Jiang; Mingjie Li; Jinghang Ding; Chuang Mei; Xin Xiong (Bioresource Technology, 2026)

Physiological and molecular mechanisms of blue light-regulated archeospore formation in Pyropia yezoensis - Li-Fei Yang; Yue-Ting Pan; Hong-Chang Ding; Da-Hai Gao (Aquaculture, 2026)

Cu2O@Fe Prussian blue-integrated smartphone-assisted sensing strategy for hydroquinone and bisphenol A determination - Jian-Mei Chen; Yong-Qi Ding; Yan-Hong Zhou; Zi-Xuan Bai; Xiao-Tong Yang; Xin Huang; Shuai Li; Feng-Zhan Sun (Food Chemistry, 2026)

Diurnal differences in the effects of heat exposure on renal function: A randomized controlled crossover trial - Jintao Liu; Yuefang Li; Yarui Fan; Xiaojie Zou; Hung Chak Ho; Danfeng Zhang; Jing Zhang; Jian Song; Xu Wang; Xiuxiu Ding; Xiaoyu Jin; Lijuan Qiu; et al. (Environmental Research, 2026)

Inhibition of RBM25 preserves cardiac mitochondrial homeostasis and attenuates ischemic heart failure - Shu Liu; Hong Ding; Kejuan Li; Xiaowei Zhang (Journal of Molecular Histology, 2026)

Construction of a porous-ionic-polymer encapsulated Rh-TPPTS catalyst for regioselective hydroformylation - Sen Feng; Cunyao Li; Guifa Long; Guangjun Ji; Xiaofeng Ma; Benhan Fan; Hong Wei; Xinyuan Liu; Yang Zhao; Miao Jiang; Li Yan; Yunjie Ding (Chemical Engineering Journal, 2026)

Transcriptome and metabolome analysis reveals that cuproptosis in bovine cumulus cells triggers the intercellular transmission of senescence and mitochondrial dysfunction to impair oocyte quality - Hong Xu; Tian Tian; Dan Xu; Xiaoxue Du; Rui Su; Jinghong Liang; Ying Liu; Yuqing Zhang; Chang Liu; Shuang Liang; Qingying Li; Deli Ding; et al. (Theriogenology, 2026)

Optimization and characterization of a low-toxicity trans-anethole nanoemulsion for controlling the soil-borne bacterial pathogen Ralstonia solanacearum - Yao Wang; Yonghao Liu; Lei Yang; Zichen Li; Mengxiao Xie; Deping Ke; Gui Gao; Zhijun Chen; Jiaxi Yuan; Hong Zhou; Shili Li; Wei Ding (Pesticide Biochemistry and Physiology, 2026)

The combination of near-infrared spectroscopy (NIR) and chemometrics for qualitative and quantitative detection of additives in soy sauce - Xingyu Ji; Zhi-hong Zhang; Xianxin Li; Yanhua Ding; Mouming Zhao; Haile Ma; Xianli Gao (Food Chemistry, 2026)

Performance and microbial community dynamics of an internal circulating photogranular membrane bioreactor for synthetic mariculture wastewater treatment under different hydraulic retention times - Weirun Li; Guoyu Zhang; Lingjie Li; Yiwen Ding; Hong You; Yi Ding; Jing Zhu; Zhipeng Li (Environmental Research, 2026)

Three new ent -kaurene diterpenoid glucosides from the flowers of Inula japonica Thunb. - Zheng Niu; Jia-Qi Chen; Guan-Ke Liu; Li-Qin Ding; Chun-Yan Chen; Bing-Yang Zhang; Yu-Hong Li; De-Qin Zhang; Tie Yao; Feng Qiu (Natural Product Research, 2026)

Multi-driver landslide disasters: distribution, formation, and mitigation - Shufeng Tian; Ningsheng Chen; Haitao Ding; Xiangyu Shao; Mengjie Jiao; Yongjian Li; Jiming Jin; Muhib Ullah Khan; Mingyang Wu; Xiaohu Chen; Bishal Gurung; Yongzhi Wang; et al. (Science Bulletin, 2026)

Unraveling the role of plastic polymers in PAHs emissions from municipal solid waste incineration: Quantifying contributions, synergy, and source tracers - Shuangxi Zhou; Xinyu Huang; Zhanbo Hong; Yufan Wang; Bin Zhang; Tianyang Su; Jiajia Pu; Tian Zhang; Yanlin Li; Xinran Qiu; Ling Ding; Xian Li; et al. (Journal of Hazardous Materials, 2026)

Revealing antibacterial mechanisms of a magnetic flocculation system: The multi-target disruption effect - Muxinjian Luo; Zijie Zhong; Qiang Sun; Manli Sun; Honghao Wu; Wei Ding; Hong Li; Huaili Zheng (Journal of Hazardous Materials, 2026)

Rapid determination of diesel density using near-infrared and mid-infrared spectroscopy data fusion modelling - Chaomin Ding; Ying Kan; Anni Liu; Xiaoyan Guo; Zhengdong Zhang; Junting Tong; Ke Li; Fan Liu; Xiaoping Song; Yong Yan; Qi Li; Tao Hong (Fuel, 2026)

Recombinant bovine αs1-casein as an enhanced precursor for sleep-promoting peptides: A structural, peptidomic, and molecular docking study - Long Pan; Lin-Lin Ding; Meng-Jia Song; Xiang-Li Mu; Ai-Mei Liao; Yin-Chen Hou; Ji-Hong Huang; Guang-Hai Yu (Food Bioscience, 2026)

Interfacial hydrogen bonding as a key driver for selective phenolic compounds removal via Mg(OH)2-catalyzed peroxymonosulfate activation - Yuan Ding; Jiachun Cao; Shiting Li; Hong Huang; Honggen Peng; Xiaoxiao Fu; Chunyang Nie; Zhimin Ao (Chemical Engineering Journal, 2026)

RDO3 REPRESSOR 27, a new MED25 allele, regulates seed dormancy dependent on DOG1 and ABA pathways in Arabidopsis - Yue Yang; Xiao-Ying Li; Run Ding; Hong Cao; Yongxiu Liu; Yu Li (Planta, 2026)

LncRNA MNX1-AS1 drives the progression of non-small cell lung cancer and serves as a ceRNA to target COMMD8 by sponging miR-218-5p - Gao-Feng Liu; Li Zhou; Yu-Bo Zhao; Jia-Hong Tang; Qing-Yuan Li; Xiao-Yong Ding; Xiao-Zhen Zhang; Su-Juan Cui; Yong Zhang; Zhen-Wei Sun (Journal of Molecular Histology, 2026)
The role and mechanistic action of MNX1-AS1 in non-small cell lung cancer (NSCLC) remain unclear. This study aimed to investigate the function of MNX1-AS1 in the progression of NSCLC. A total of 40 paired tumor and adjacent lung tissue samples from patients with NSCLC were collected to investigate the expression of MNX1-AS1. H1299 and HCC827 cells were transfected with sh-MNX1-AS1, shRNA-NC, miR-218-5p mimic, mimic-NC, pcDNA3.1-COMMD8, or empty vector (pcDNA3.1). The expression of MNX1-AS1, miR-218-5p, and COMMD8 was detected using quantitative real-time PCR (qRT-PCR). Cell proliferation was evaluated using CCK-8 assays, while cell migration and invasion were evaluated using Transwell assays. Dual-luciferase reporter and RNA pull-down assays were performed to validate the targeting interactions between MNX1-AS1 and miR-218-5p, as well as between COMMD8 and miR-218-5p. In vivo, a nude mouse model was established: tumor volume and weight were measured after four weeks. Gene expression in tumor tissue was quantified using qRT-PCR, and Ki-67 expression was evaluated using immunohistochemistry. MNX1-AS1 expression was significantly upregulated in NSCLC tissues ( P < 0.05) and was correlated with poor prognosis in NSCLC patients. MNX1-AS1 knockdown markedly suppressed the viability, migration, and invasion of H1299 and HCC827 cells ( P < 0.05). Mechanistically, MNX1-AS1 acted as a molecular sponge for miR-218-5p, thereby relieving miR-218-5p-mediated repression of its direct target COMMD8 ( P < 0.05). Functional rescue experiments revealed that miR-218-5p silencing or COMMD8 overexpression partially reversed the inhibitory effects of MNX1-AS1 knockdown on the cell viability, migration, and invasion of H1299 and HCC827 cells. In vivo, sh-MNX1-AS1 significantly reduced tumor volume and weight ( P < 0.05). Moreover, the expression of MNX1-AS1, COMMD8, and Ki-67 were downregulated, while the expression of miR-218-5p was upregulated in sh-MNX1-AS1 tumor tissues ( P < 0.05). MNX1-AS1 promotes the progression of NSCLC by modulating the miR-218-5p/COMMD8 axis.

Topology guided and feature decoupled optical-SAR cross-modal knowledge distillation for rapid post-flood water extent mapping - Yinhaibin Ding; Jingsheng Lei; Yang Li; Lanqing Zhang; Huitao Sun; Yanyan Du; Lu Xu; Hong Zhang (International Journal of Remote Sensing, 2026)

Endothelial VEGFR2 insufficiency promotes the transition of lymphatic to hematopoietic transcriptional programs - Taotao Li; Xudong Cao; Fei Zhou; Xiujuan Li; Wenjuan Ma; Xiuyan Zhang; Haoyu Zhong; Beibei Xu; Man Chu; Xiwen Jia; Kai Ding; Xin Shen; et al. (Angiogenesis, 2026)

Spatiotemporal variation in soil available potassium in Central-Western China - Xiaoyan Li; Xiaodong Song; Chengchao Yang; Ying Xiao; Yunpeng Hong; Shuming Ding; Xudong Wang; Jiaojiao Lei (Environmental Monitoring and Assessment, 2026)

Systematic analysis of photogranulation characteristics during start-up of a photogranular sequencing batch bioreactor for mariculture wastewater treatment - Weirun Li; Zhipeng Li; Guoyu Zhang; Lingjie Li; Yixuan Yang; Shuyu Zhao; Hong You; Yi Ding; Jing Zhu (Marine Pollution Bulletin, 2026)

Toward high-precision, low-consumption bulk analysis: advancements in extraterrestrial sample studies - Ding-Shuai Xue; Shun Guo; Yan-Hong Liu; Dan-Ping Zhang; Yong-Gang Yao; Bo Wan; Xian-Hua Li (Science Bulletin, 2026)

Localized temperature oscillation induced by laser scanning for efficient and stable CO2 methanation - Tong Wu; Jinbao Xia; Yue Li; Xue Dong; Zhiqiang Rao; Yanfeng Li; Chuanshun Xing; Lili Zhao; Wenqiang Gao; Wei Xia; Baitao Zhang; Hong Liu; et al. (Science Bulletin, 2026)

A novel mitochondrial OMA1-DELE1-HRI axis mediates polystyrene microplastics-induced blood-testis barrier dysfunction - Rong Wang; Zhen Tian; Chen Chen; Ming-Ming Zhang; Ding-Qiang Peng; Ke-Xin Liu; Yu-Tong Ren; Shuai Lin; Qiang Hong; Yan-Li Ji; Yuan-Hua Chen (Journal of Environmental Sciences, 2026)

Knowing when to stop: Threshold effects of human disturbance on ecosystem health in the Taihu Basin, China - Zhifan Ding; Hanyu Hu; Qinghua Xu; Xiaolan Hong; Mingcheng Li; Jiayu Qin; Ying Zhu; Hui Wang (Environmental Impact Assessment Review, 2026)

Long working hours increase the risk of insufficient dietary diversity: Findings among online ride-hailing drivers - Binshuo Hu; Cheng Chang; Xin Song; Zhihui Wang; Xiaoshun Wang; Xiaowen Ding; Hong Yu; Li Guan; Dongsheng Niu; Jue Li; Rui Guan; Tenglong Yan (Appetite, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Synthesis, characterization, and antimicrobial properties of 8-Hydroxyquinoline-based group 4 metal complexes for plant pathogen control - Tiankun Zhao; Baoqing Lv; Yinan Ding; Dongyu Mei; Jing Ma; Qi Zhang; Li Zhang; Qipin Qin; Zhongduo Yang; Shanjia Li; Isabel Correia; Hong Liang; et al. (Pesticide Biochemistry and Physiology, 2026)

Stomatal width and vascular bundle anatomy govern foliar uptake and phloem transport of atmospheric Pb in wheat - Liu-Xu Feng; Xiang-Yu Li; Pei-Pei Gao; Yan Li; Gui-Li Hua; Ding-Hao Li; Li-Ping Geng; Xiao-Min Wang; Hong-J. Di; Wen-Ju Liu; Pei-Ying Xue (Journal of Hazardous Materials, 2026)

Enhanced piezoelectric catalytic degradation of tetracycline by -NO2-functionalized MIL-101(Fe) via modulating electron polarization - Yangyang Ding; Runchen Zhu; Jialiang Zhou; Weihong Xu; Fakang Pan; Dandan Yang; Junyong He; Zijian Wu; Yulian Li; Chao Xie; Yahui Li; Jiandong Lu; et al. (Journal of Environmental Chemical Engineering, 2026)

Impaired Glymphatic-Meningeal Lymphatic Function in Patients with Spontaneous Subarachnoid Hemorrhage - Jianan Lu; Miao Lin; Heping Tian; Yibo Liu; Bingrui Zhu; Jin Mao; Jiahao Zhang; Haocheng Zhang; Sixuan Tian; Xu Li; Ding Xu; Chenhan Ling; et al. (Translational Stroke Research, 2026)

Development of a self-assembling aggregation-induced emission nanoprobe for targeted therapy and real-time imaging in non-small cell lung cancer - Zhen Ren; Shuai Li; Tong Cui; Tianjie Zhu; Dapeng Ding; Jingyuan Zhao; Hong Yuan (Journal of Photochemistry and Photobiology B: Biology, 2026)

Deciphering solute transport in crack networks-clay matrix systems: Insights from experiments and numerical modeling - Li Luo; Yong He; Gezhi Ou; Zhao Zhang; Kao-fei Zhu; Xiang-hong Ding (Engineering Geology, 2026)

Herbiconiux dendrobii sp. nov., a Novel Bacterium Isolated from Dendrobium devonianum Sawdust Substrate - Hao Liang; Fang Zhao; Hong-Bo Zha; Zhang-Gui Ding; Le-Le Li; Jiang-Yuan Zhao; Zhi-Ran Zhao; Min Zheng; Jian-Sheng Cheng; Hui-Cheng Deng; Shu-Kun Tang; Ming-Gang Li (Current Microbiology, 2026)

Comprehensive understanding of new particle formation in China through advanced modeling - Jiewen Shen; Bin Zhao; An Ning; Wei Nie; Chao Yan; Yuyang Li; Runlong Cai; Alfonso Saiz-Lopez; Manish Shrivastava; Biwu Chu; Da Gao; Nanna Myllys; et al. (Science Bulletin, 2026)

PMF-driven component-particle association framework establishes dynamic baselines for objective risk assessment of coastal metal pollution - Hanyi Li; Jiajia Wu; Kang Mei; Shengjie Wu; Mingyu Guo; Haoliang Lu; Jingchun Liu; Zhenhua Ding; Chonglin Yan; Hualong Hong (Process Safety and Environmental Protection, 2026)

Unlocking sustainable water decontamination: Controlled sulfite release from solid calcium sulfite for enhanced electrochemical arsenite oxidation - Chaojie Wang; Hejiao Zhang; Manli Sun; Huaili Zheng; Hong Li; Wei Ding (Journal of Hazardous Materials, 2026)

Engineering Cu-enhanced Mn-based Prussian blue analogue with boosted dual-redox activity for efficient and fast capacitive deionization - Zhiqiang Wu; He Ren; Hao Zhou; Jianeng Ji; Haiyun Ding; Chunyan Li; Minjie Shi; Ying Hong; Jun Yang (Desalination, 2026)

The Influence of M1 and DLPFC iTBS on BCI Performance: A TMS and fNIRS Study - Jing Chen; Ya-wen Li; Shan-tong Yao; Yu-hong Huang; Wen-ming Ma; Zhi-hong Li; Yue Lan; Guang-qing Xu; Qian Ding (Translational Stroke Research, 2026)

Migration behaviour of heavy metals and vitrification characteristics in melting of municipal solid waste incineration fly ash - Quanming Li; Yajie Gao; Chao Geng; Xianfeng Shi; Hong Zhang; Cheng Chen; Yukai Wang; Jiaqi Chang; Yajie Wang; Ziyi Ding (ENGINEERING Environment, 2026)

Epidemiological and evolutionary analysis of porcine circovirus type 2 within pig populations in central China during 2021-2024 - Jia-Xin Li; Hao Li; Feng-Shuo Wang; Yun-Yun Li; Guang-Cai Wang; Hong-Lei Zhang; Xue-Yan Ding; Lan-Lan Zheng; Shi-Jie Ma (Archives of Virology, 2026)

Rapid and Simple Detection of Enterocytozoon Bieneusi Using Lateral Flow Assay Based on Recombinase Polymerase Amplification or Nested PCR Combined with CRISPR–Cas12a - Yi-Yang Liu; Yue-Rong Lv; Jun-Tao Jia; Rong Zhang; Bo Yang; Shi-Yuan Xue; Hasi Bayaer; Alateng Bagen; Rui-Bin Chen; Siqin Tunala; Rui Wang; Yu-Lin Ding; et al. (Acta Parasitologica, 2026)

Moderately quaternized starch-derived polymers for synchronous bacterial removal and sustained inactivation: Enhancing disinfection and unveiling the synergistic mechanism - Manli Sun; Bing Bao; Wei Ding; Zhanmei Zhang; Qixin Pan; Huaili Zheng; Hong Li (Journal of Hazardous Materials, 2026)

Multifunctional nanocomposite packaging films enabled by tannic acid-modified chitin nanocrystals for fruit preservation - Rongli Li; Tongjun Yang; Mingtao Ding; Hong Yu; Shunlin Yang; Xiaochen Pan; Lihua Zhang; Haibo Xie (Food Hydrocolloids, 2026)

Alterations in cardiovascular biomarkers and gut microbiome associated with night shift work: Insights from the Chinese platform workers study - Tenglong Yan; Li Rong; Siyuan Wang; Xin Song; Binshuo Hu; Zhihui Wang; Xiaoshun Wang; Xiaowen Ding; Rui Guan; Hong Yu; Dongsheng Niu; Ying Zhang (Environmental Research, 2026)

Investigation on Rock Fragmentation and Energy Dissipation Under Sandstone Blasting - Xudong Li; Zhongwei Chen; Chuan He; Guowen Xu; Bo Wang; Yanzhi Ding; Zongzhi Zhao; Zhixian Hong (Rock Mechanics and Rock Engineering, 2026)

Effects of earthworms on soil virus-associated ARGs and resistance phenotypes in long-term field cropping systems - Ying Ding; Bo-Wen Liu; Di Wu; Hong-Zhe Li; Shuai Du; Dong Zhu (Journal of Hazardous Materials, 2026)

Unique ecological functions of viral communities potentially influence microbial adaptability in deep-sea ferromanganese nodule deposits - Yu-Kang Li; Ge-Yi Fu; Zhen Rong; Jun-Qing Chen; Zhi-Hao Ding; Zu-Xin Zhang; Hua-Hua Jian; Wen-Sheng Shu; Yue-Hong Wu; Xue-Wei Xu (Journal of Hazardous Materials, 2026)

Highly efficient activation of sulfite with robust Mn-MOF catalysts for arsenite oxidation: Formation and contribution of Mn(V) - Chao Liu; Chaojie Wang; Bingxu Chen; Haitao Lu; Wei Ding; Hong Li (Chemical Engineering Journal, 2026)

Regulation of grain protein content by the amino acid permease gene OsAAP4 in rice - Ming-Xin Li; Feng-Lin Huang; Jin-Hong Lin; Jia-Yi Qu; Guo-Feng Wan; Gen-Cai Song; Jing Zhao; Yan Peng; Zhen-Ning Teng; Ling Liu; Cheng Zheng; Hou-Xiong Wu; et al. (Theoretical and Applied Genetics, 2026)

Psychromicrobium ferritrahens sp. nov., A Novel Actinobacterium Isolated from Decayed Wood in Shizong County, China - Lin-Bo Zhang; Jiang-Yuan Zhao; Yong-Jie Zeng; Hong-Bo Zha; Lin Gong; Pei-Wen Yang; Zhang-Gui Ding; Ming-Gang Li; Shun-Bo Gao; Le-Le Li; Shu-Kun Tang (Current Microbiology, 2026)

Phyllosphere to soil: How long-term fencing reshapes grassland microbial community construction and the functional genes - Jian Li; Yu Zhu; Daniel F. Petticord; David W. Frey; Lijie Huang; Ming-Kang Jin; Michiel Op de Beeck; Quan-Hui Ma; Shu-Huan Jin; Hong Ying; Xi-Mei Xue; Ling Wang; et al. (Agriculture, Ecosystems & Environment, 2026)

Marine chitin valorization by ionic liquids and deep eutectic solvents: Dissolution, green extraction and conversion - Lihua Zhang; Yunqi Li; Rongli Li; Hong Yu; Shunlin Yang; Mingtao Ding; Haibo Xie (Bioresource Technology, 2026)

Tumor Necrosis Factor Alpha-Mediated Interaction Between Microglia and Müller Cells Exacerbates Retinal Ganglion Cell Damage in Experimental Glaucoma - Shu-Ying Li; Hong Zhou; Guoli Zhao; Wen-Wen Ding; Yu Zhang; Yong-Chen Wang; Fang Li; Yanying Miao; Xing-Huai Sun; Zhongfeng Wang (Neuroscience Bulletin, 2026)

Precise molecular spacer engineering for tumor-responsive pKa tuning: a pan-cancer imaging platform for evaluating tumor microenvironment reprogramming capability - Hong Zhang; Fei-Fan Xiang; Ding-Heng Zhou; Yan-Hong Liu; Zhou-Yu Wang; Shan-Yong Chen; Xiao-Qi Yu; Kun Li (Science Bulletin, 2025)

Quantifying the sources of REE in the deep Philippine Sea: Insights from numerical modeling and field observations - Hong Che; Yi Zhong; Wenkai Guan; Qian Liu; Panfeng Li; Xue Ding; Bangqi Hu (Progress in Oceanography, 2025)

Hierarchical spatiotemporal delivery system reprograms osteoclast subtypes to promote angiogenesis and bone regeneration in steroid-induced osteonecrosis of the rat femoral head - Hongyu Quan; Taiyang Li; Chencan Ren; Yuwei He; Hongkun Xie; Zibo He; Rui Wang; Haibin Ding; Jinbao Li; Shiwu Dong; Hong Jiang (Chemical Engineering Journal, 2025)

Multiband bipolar photoresponse in Cu@CuOx@a-Ga2O3 core-shell heterostructure-based self-powered photoelectrochemical-type photodetector for secure underwater optical communication - Yixin Sun; Yan Tang; Xiuhong Jiang; Aijiang Yan; Jin Zhao; Yuchuan Wang; Jiangshuai Luo; Jili Jiang; Ke Ding; Hong Zhang; Honglin Li; Di Pang; et al. (Chemical Engineering Journal, 2025)

Enhanced Removal of Phorate in Polluted Soil by Co-Solvent-Augmented Alkaline Activation of Persulfate - Tingting Lv; Hong Wang; Ding Li; Ruihai Li; Chengliang Yang; Wei Zhao; Zhenyu Cui; Jianxin Li (Water, Air, & Soil Pollution, 2025)

Association of Serum Neurofilament Light and Glial Fibrillary Acidic Protein with Cerebral Small Vessel Disease in Nondemented Middle-to-Old Aged Population - Xiao-Hong Huang; Feng Gao; Jing Yuan; Ding-Ding Zhang; Mei-Jun Shu; Fei-Fei Zhai; Fei Han; Ming-Yu Tang; Ming-Li Li; Li-Xin Zhou; Jun Ni; Ming Yao; et al. (Translational Stroke Research, 2025)

Decades’ progress and prospects on maize functional genomics and molecular breeding - Qing Li; Jinsheng Lai; Jian Chen; Lin Li; Weibin Song; Beibei Xin; Hainan Zhao; Yingjie Xiao; Feng Tian; Gang Li; Yameng Liang; Lei Liu; et al. (Science China Life Sciences, 2025)

3-TYP protects against heart failure with preserved ejection fraction by inhibiting Sirtuin 3 - Ziwei Zhu; Yuqin Wang; Jianshu Chen; Yongnan Li; Hong Ding; Wenbin Wu; Xiaowei Zhang (Journal of Molecular Histology, 2025)

Harnessing Plant Essential Oils to Combat Acinetobacter baumannii: Research Progress in Antimicrobial Mechanisms and Therapeutic Prospects - Shu-Yun Wei; Yu Sun; Qing Lu; Zhen Liang; Tao Zhu; Yu-Long Li; Ding-Hui Xu; Cai-Ying Li; Feng-Lan Feng; Hong Zeng (Current Microbiology, 2025)

Soil pH and bacterial diversity synergistically regulate trace element transfer and accumulation in soil-rice systems - Ying Ding; Bao-Min Yao; Hong-Ling Chen; Dong-Li Sun; Zi-Yang Pan; Qing Zeng; Chang-Chun Zhai; Yuan-Kun Liu; Guo-Xin Sun (Soil Ecology Letters, 2025)

Pathways of Adverse Effect on the Blood-Testis Barrier by Environmental Pollutants - Xicha Lin; Yuanlu Ding; Wei Zheng; Yingyi Yao; Nan Wang; Minjie Li; Liang-Hong Guo (Reviews of Environmental Contamination and Toxicology, 2025)

Revisiting fermented buckwheat: a comprehensive examination of strains, bioactivities, and applications - Huan Guo; Hang Li; Yue Xiao; Ding-Tao Wu; Ren-You Gan; Zhiliang Kang; Yina Huang; Hong Gao (Critical Reviews in Food Science and Nutrition, 2025)

Effects of interface roughness and layer thickness on the cracking characteristics of fine-grained coral soil - Junyu Ren; Xuanming Ding; Huaqiang Fang; Hong Wang; Yifu Li (Marine Georesources & Geotechnology, 2025)

A protein structure-dependent fluorescent probe for real-time β-lactoglobulin detection - Xian-Ting Yan; Wen-Xuan Qin; Kai-Li Chang; Hong-Kai Bian; Xin-Yu Pan; Xiang Ding; Wen-Bo Liu; Qing Wang (Food Chemistry, 2025)

Basal-topdressing trade-offs in maize production: Lower current N losses versus elevated soil residual N and subsequent losses in the Northeast China - Zheng Liu; Wenli Zhou; Tujin Wang; Hong Ren; Baoyuan Zhou; Zaisong Ding; Xinbing Wang; Congfeng Li (Field Crops Research, 2025)

Sugar-based block copolymer/carbon nanotube nanocomposites for thermoelectric applications - Yen-Yu Chen; Hong Li; Chih-Jung Lin; Koshin Tanaka; Meng-Hao Lin; Shao-Huan Hong; Min-Chi Fu; Jian-Fa Ding; Yu-Jane Sheng; Redouane Borsali; Tsuyohiko Fujigaya; Cheng-Liang Liu (Chemical Engineering Journal, 2025)

Multifunctional hierarchical BN/MXene-Fe3O4 aerogel for efficient thermal management and ultra-broadband microwave absorption - Xin-Miao Liang; Qi-Fan Xuan; Hong-Hao Li; Peijia Ding; Yu Zhang; Martin C. Koo; Chen-Ming Liang; Shu-Hao Yang; Pei-Yan Zhao; Dongfeng Zhang; Guang-Sheng Wang (Chemical Engineering Journal, 2025)

Establishment of succinic acid production in recombinant Kluyveromyces marxianus enhanced by AI-guided enzyme specificity engineering and redox-controlled fermentation optimization - Du-Wen Zeng; Yi-Fan Zhu; Yuan-Hong Jiang; Ya-Hao Ding; Zhen-Zhi Wang; Kai Li; Sha Liao; Ya-Chao Fan; Lin Zhang; Yu Guang Wang; Xin-Qing Zhao (Chemical Engineering Journal, 2025)

Chitin whisker liquid crystal hydrogel embedded with polyacrylic acid templating osteoid-like Bouligand structure for guiding internal mineralization - Ruixi Zhang; Yiting Luo; Wei Zhou; Xinxin Huang; Runshan Huang; Wei Wen; Shan Ding; Hong Li; Mingxian Liu; Changren Zhou; Binghong Luo (Carbohydrate Polymers, 2025)

Investigation of the South Atlantic Anomaly (SAA) by proton flux variabilities based on 6 years’ CSES data - Lu Wang; Zhenxia Zhang; Xinqiao Li; Zhenghua An; Yanbing Xu; Ping Wang; Hong Lu; Xiaoyun Zhao; Dali Zhang; Xiaohua Liang; Zhiqiang Ding; Shujie Li; et al. (Science China Earth Sciences, 2025)

Calcium Signaling in Astrocytes and Its Role in the Central Nervous System Injury - Xinyue Li; Lu Ding; Hong Nie; David Y. B. Deng (Molecular Neurobiology, 2025)

Facile One-Pot Synthesis of Folic Acid-Derived Carbon Dots for Selective “on-off-on” Fluorescence Detection of Ag+ and Glutathione with High Sensitivity - Lijuan Chen; Yuting Ding; Changchang Chen; Xiaoyan Jiang; Danni Yang; Jingwen Li; Hong Liu; Linlin Yang (Journal of Fluorescence, 2025)

Avian HEV triggered egg decline: Viral-host, immune-neuroendocrine mechanisms in layers - Beibei Zhang; Siping Kuang; Zhiyang He; Jing Zhang; Shuli Li; Hong Duan; Zhenghai Ma; Juntao Ding (Veterinary Microbiology, 2025)

Curcumin-mediated photodynamic treatment efficiently inhibits Bacillus cereus and extends the shelf-life of flat rice noodles - Hao-Ran Ji; Jia-Jun Yan; Zi-Hui Chen; Wen-Li Shi; Li-Wen Chen; Juan Wang; Yu Ding; Ai-Min Jiang; Bing Du; Cai-Hu Liao; Hong-Tao Lei; Quan Zhou; et al. (Food Research International, 2025)

An electrochemiluminescence biosensor for the screening of environmental estrogens using a peptide probe targeting the activated estrogen receptor - Jiali Li; Yuanlu Ding; Jiateng Ma; Chuang Liu; Minjie Li; Liang-Hong Guo (Environmental Research, 2025)

A numerical study of the symplectic FDTD(,) method combined with matrix exponential technique for anisotropic magnetized plasma - Guilin Hou; Guoda Xie; Wenjie Ding; Yingsong Li; Yang Hong; Zhixiang Huang (Computer Physics Communications, 2025)

Quasi-solid electrolyte constructed by fiber-guided continuous growth of core-shell MOF architectures for dendrite-free lithium metal batteries - Guoxu Wang; Wenxin Li; Xiuwen Wang; Xiaoyan Liu; Wei Ding; Chengbiao Wei; Hong Liu; Mai Zhang; Feng Lin (Chemical Engineering Journal, 2025)

Chemical constituents from the stems of Daphniphyllum angustifolium Hutch. and their chemotaxonomic significance - Xiao-Juan Huang; Heng-Gang Zhang; Xiao-Hong Li; Yu-Bin Wei; Khalid-Hassan Mohamed; Chang-Qin Yin; Hao-Fei Yu; Cai-Feng Ding; Lan-Chun Zhang (Biochemical Systematics and Ecology, 2025)

Reliability assessment of offshore wind turbine gears under multiple failure modes using deeply coupled adaptive Kriging based-generalized subset simulation - Yuan-Zhuo Ma; Chuang Li; Chen-Xu Li; Bo-Feng Xu; A-Nai Ding; Hong-Shuang Li; Zhen-Zhou Zhao (Ocean Engineering, 2025)

Mn/Fe bimetallic MOF-driven sulfite activation for synergistic non-radical oxidation and chemisorption of arsenite: Involvement of high-valent Fe(IV)/Mn(V) species - Qixin Pan; Chao Liu; Cheng Zhang; Huaili Zheng; Wei Ding; Hong Li (Journal of Hazardous Materials, 2025)

Pectic polysaccharides from unripe and mature kiwifruit alleviate ulcerative colitis by modulating gut microbiota and restoring the intestinal barrier - Kai-Xin Jiang; Jin-Lei Geng; Qin Yuan; Jie Li; Wen Liu; Hong-Yan Liu; Yi-Chen Hu; Liang Zou; Shengpeng Wang; Ding-Tao Wu (Food Bioscience, 2025)

Association of long-term PM2.5 and its components exposure with ovarian hyperstimulation syndrome risk in assisted reproductive technology patients - Jia-Liang He; Rui-Ling Liu; Yu-Ling Hu; Quan-Zi Yao; Zhi-Lei Xu; Li-Hong Geng; Tong Wang; Xin Luo; Ying-Ling Yao; Yong-Jia Zhang; Xue-Jiao Wang; Zhao-Hui Zhong; et al. (Environmental Pollution, 2025)

Oral administration of nanozyme-armed probiotic Escherichia coli Nissle 1917 with ROS scavenging for inflammatory bowel disease therapy - Tiantian Cui; Bing Li; Zhaoyang Lou; Kai Yang; Kaijin Yan; Danhong Ding; Hong Ge (Chemical Engineering Journal, 2025)

Gelatin-based anisotropic hydrogels for flexible sensors and bio-electrodes - Linfa Li; Yu Sun; Jingkang Ding; Changyong Wang; Yu Xiang; Bingyan Guo; Lei Liang; Xiaochen Lu; Hong Zhang; Fanglian Yao; Junjie Li (Chemical Engineering Journal, 2025)

Unraveling the diversity of bile acid modifications by integrative mass spectrometry approaches - Nan Xing; Yu-Fei Wang; Xue Ding; Hong-Li Tan; Yi-Fang Li; Guo-Xiang Sun; Rong-Rong He; Wan-Yang Sun (Science China Life Sciences, 2025)

Multi-centric clinical implementation of the remote and automated quality control programme for digital imaging in Malaysia: challenges and pitfalls - Vinoshah S. Ravichandran; Nur Ammi Hamzah; Li Kuo Tan; Virginia Tsapaki; Olivera Ciraj Bjelac; Noramaliza Mohd Noor; Nur Syahiirah Mohamad Mokhtar; Nur Hasyimah Abd Rashid; Adiela Saiful Fazad; Nur Hafizah Zakaria; Siti Norsyafiqah Mohd Mystafa; Wan Nur Ain Wan Ghazali; et al. (Physical and Engineering Sciences in Medicine, 2025)

New polyketides and cytotoxic alkaloids from the mangrove endophytic fungus Talaromyces sp. SAF14 - Hong Li; Cankai Lin; Kaixin Chen; Zhihui Zhou; Zanhong Chen; Bo Ding; Hongbo Huang; Yiwen Tao (Natural Product Research, 2025)

Insights into the development of quaternized starch-derived polymers for simultaneous flocculation and bacterial inactivation: Mechanism and directed regulation - Manli Sun; Hong Li; Kexin Wang; Chao Hu; Xincheng Jiang; Wei Ding; Yuxin Zhang; Huaili Zheng (Water Research, 2025)

Isolation of dihydroagarofuran sesquiterpene from the fruits of Tripterygium hypoglaucum and evaluation of their anti-inflammatory activity - Shi-Li Wu; Xing Yang; Wen-Xiu Ning; Gang-Yun Wu; Xin-Yu Dai; Yu Zhang; Duo-Zhi Chen; Xiao Ding; Hong-Ping He; Wei Zhou; Xiao-Jiang Hao (Phytochemistry, 2025)

Efficient solar to acetate conversion in microbial electrosynthesis with CQDs/FeOOH/g-C3N4 photocathode and CQDs/FeOOH/BiVO4 photoanode coordination under visible light - Tianshun Song; Hong Ding; Kang Zhang; Xiang Ling Li; Jingjing Xie (Journal of Environmental Chemical Engineering, 2025)

Vanadium isotope fractionation in mantle rocks: Constraints from peridotites and pyroxenites - Cheng-Yi-Hong Liu; Dmitri A. Ionov; Fang Huang; Chunhui Li; Xin Ding (Geochimica et Cosmochimica Acta, 2025)

Cultured biomass enhances the flavor and nutrition characteristics of biomass/plant hybrid cultured meatballs - Zi-Qing Meng; Chang-Bo Tang; Tian-yi Tao; Wenjuan Song; Chun-Bao Li; Jun Qi; Shi-jie Ding; Guang-Hong Zhou (Food Research International, 2025)

Impact of environmental salinity on the MAPK-NFAT5 pathway in Trachemys scripta elegans and its role in osmoregulaton - Xin Niu; Yingnan Lu; Yue Yuan; Jiao Li; Yunjuan Xiao; Haitao Shi; Meiling Hong; Li Ding (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Synergistic nano-bioeffects: Dual impact of bisphenol-derived carbon dots on environmental health and antimicrobial therapy - Siyuan Hu; Xinzhong Zhang; Jiayu Li; Xiang Wang; Chen Gao; Jiatong Zhou; Jing Cai; Miaomiao Yin; Rufang Zhao; Xin Ding; Wei Hong; Yanjun Hu (Chemical Engineering Journal, 2025)

CD39 activities in the treated acupoints contributed to the analgesic mechanism of acupuncture on arthritis rats - Yu-Jia Li; Jie Lin; Si-Qi Tang; Wei-Min Zuo; Guang-Hong Ding; Xue-Yong Shen; Li-Na Wang (Purinergic Signalling, 2025)

Karst Trough Control of Solute Transport Processes at Two Karst Groundwater Flow Systems, Western Hubei, Central China - Yi’an Wang; Ruichao Zhao; Lin Ding; Shuai Xiong; Yin Li; Jianwei Bu; Wei Chen; Hong Zhou; Wei Liu (Journal of Earth Science, 2025)

Coupling soil bacterial and fungal community traits to multifunctionality in grassland ecosystem - Chenxiao Ding; Yaowei Liu; Marcela Hernández; Han Sun; Shuo Jiao; Hong Pan; Tida Ge; Kankan Zhao; Qichun Zhang; Jianming Xu; Yong Li (Agriculture, Ecosystems & Environment, 2025)

A redox-modulating coating with multi-enzyme activity on engineered nanoparticles: An effective strategy for enhancing the control of plant bacterial diseases - Zhenghao Ding; Liwei Liu; Qingqing Song; Lin Chen; Guangdi Wang; Hong Li; Xinxin Tuo; Zhibing Wu; Xiang Zhou; Song Yang (Chemical Engineering Journal, 2025)

Increasing the light–dark ratio enhances nitrogen removal performance by altering the mechanism in photogranules - Xiaodi Xing; Jing Zhu; Zhipeng Li; Guoyu Zhang; Weirun Li; Haili Tan; Binghan Xie; Yixuan Yang; Shuyu Zhao; Yi Ding; Hong You (Bioresource Technology, 2025)

Multi-scale characteristics and statistically associated factors of ozone pollution in Hangzhou based on machine learning - Yu-ting He; Tao Ding; Ru Yi; Yuan-yuan Wang; Yi Fu; Cheng-kai Tu; Hong-yan Fang; Jin-ye Li; Ming Zhang (Atmospheric Pollution Research, 2025)

Interfacial system optimization and dynamic self-healing for solid-state lithium metal batteries with high critical current density and long-term cycling stability - Kailiang Yu; Manying Cui; Qidi Wang; Hong Liu; Limin Liu; Yujia He; Pengfei Li; Juntao Gao; Xiangpeng Kong; Wandong Li; Caizhong Zhang; Kai Xi; et al. (Chemical Engineering Journal, 2025)

The recruitment of alkaline phosphatase-positive endogenous neural stem cells enables robust neurogenesis and neural pathways reconstruction following spinal cord injury - Rong-Jie Wu; Jia-Lin Liu; Zheng-Hong Chen; Jing Xu; Ying Ding; Hai-Yang Yu; Chuang-Ran Wu; Shang-Bin Yang; Rui Liu; Yi-Nan Guo; Yue Yang; Ting-Ting Wu; et al. (Chemical Engineering Journal, 2025)

Per- and polyfluoroalkyl substances (PFAS) in drinking water systems in the lower Yangtze River: source, fate, and health risk assessment - Yuan Hong; Qin Ding; Tingting Yang; Xiaoqin Li; Ninghui Song; Juan Zhang (Environmental Geochemistry and Health, 2025)

Study on automatic berthing of large under-actuated vessel with multi-tug collaboration - Guoquan Chen; Chong Ding; Jian Yin; Hong Zhu; Yuqin Li (Ocean Engineering, 2025)

Mode transitions in Hall effect thrusters by Varying duty ratio under pulsating operation - Haochen Ma; He Zheng; Tiance Liang; Jiapeng Li; Liqiu Wei; Liang Han; Hong Li; Yongjie Ding (Advances in Space Research, 2025)

Temporal Dynamics of Genetic Diversity in Protected and Unprotected Wild Rice ( Oryza rufipogon ) Populations: Implications for Conservation - Zhi‐Zhou He; Wen‐Wen Shao; Olivier Honnay; Hui Liao; Hao Chen; Jing Liu; Shan‐Shan Dong; Ding Li; Guo‐Zhen Fan; Yao Zhao; Jun Rong; Yan Liu; et al. (Molecular Ecology, 2025)
Genetic diversity is vital for population survival, yet there is a paucity of studies focusing on the effectiveness of establishing protected areas for maintaining the population genetic diversity of threatened plant species. To evaluate the effectiveness of in situ conservation measures, we used simple sequence repeats (SSR) and single nucleotide polymorphisms (SNP) markers to monitor temporal dynamics in genetic diversity of the threatened wild rice Oryza rufipogon in both protected and unprotected populations in China between 2001 and 2020. Unprotected populations tended to have decreased census population sizes ( Nc ) compared to protected populations, although they both showed a reduction in effective population size ( Ne ). While allele diversity and expected heterozygosity remained stable, several populations, especially those without protection, exhibited a significant decrease in observed heterozygosity ( Ho ) and an increase in inbreeding ( F IS ). The level of genetic differentiation between populations did not change over time, but the number of private alleles increased and Ne varied in several populations, indicating the effects of genetic drift. Indicators for temporal trends in Ho , F IS , and Ne revealed that both protected and unprotected populations are facing warnings of declining genetic diversity, although some protected populations remain resilient, reflecting the genetic lag behind Nc change. Overall, these findings highlight the effectiveness of in situ conservation efforts in maintaining population size and genetic diversity, yet we also show the necessity of lasting population dynamics monitoring, using different genetic indicators.

Dynamic effects of Aeromonas sobria infection on intestinal morphology, microbiota and goblet cells of rainbow trout (Oncorhynchus mykiss) - Li-Ping Liu; Peng-Tian Kang; Feng-Yuan Ding; Dong-Hong Shao; Bao-Shan Wang; Juan Yang; Wen-Hui Gao; Wang-Dong Zhang; Wen-Hui Wang; Ji-Xing Liu (Aquaculture, 2025)

Thioketal-photocage: a universal modification strategy for constructing new photochemical tools for real-time imaging in living cells - Ding-Heng Zhou; Shan-Yong Chen; Yan-Zhao Liu; Hong Zhang; Jun-Mei Li; Qian Zhou; Fei-Fan Xiang; Xiao-Qi Yu; Kun Li (Science Bulletin, 2025)

Long-term plastic film mulching promotes microplastic accumulation and alters gross nitrogen transformation in soil - Jinrui Zhang; Kai Wang; Tianxiang Hao; Jinbo Zhang; Christoph Müller; Perrine Florent; Hong Yan; Siyang Ren; Kaijing Qu; Kaige Ren; Jingjing Li; Yiting Su; et al. (Applied Soil Ecology, 2025)

Accurate determination of halogens in geological materials using an automated pyrohydrolysis system with a liquid nitrogen cold trap - Ding-Shuai Xue; Shun Guo; Yan-Hong Liu; Dan-Ping Zhang; Di Zhang; Xiao-Guang Li; Shan-Ke Liu (Analytica Chimica Acta, 2025)

Effects of magnetic conduction ring on the discharge characteristics and the inner cover erosion of a 100 W Hall thruster - Lei Wang; Rui Ding; Yong Wang; Liqiu Wei; Hong Li; Yongjie Ding (Advances in Space Research, 2025)

Heterocyclic pseudoguaianolide oligomers and seco-pseudoguaianolide derivatives from the inflorescence of Ambrosia artemisiifolia - Zhi Zeng; Hua-liang He; Lin Qiu; Qiao Gao; Hong-shuai Gao; Jin Xue; Xiao-nian Li; You-zhi Li; Wen-bing Ding (Phytochemistry, 2025)

A Gln alteration influences leaf morphogenesis by mediating gibberellin levels in tobacco - Qi-Li Mi; Hong-Tao Lv; Fei-Fei Huang; Li Xu; Zi-Ying Huang; Wen-Wu Yang; Mei-Yun Zou; Hai-Tao Huang; Wan-Li Zeng; Jia-Yin Zhao; Qing-Xian Chen; Yong-En Si-Tu; et al. (Journal of Plant Physiology, 2025)

A press-actuated slidable microfluidic colorimetric biosensor for Salmonella detection utilizing nickel mesh sheet and MIL-88@Pd/Pt nanoparticles - Jing Yuan; Lei Wang; Hong Duan; Siyi Ye; Ying Ding; Yanbin Li; Jianhan Lin (Food Chemistry, 2025)

Electroosmotic-driven coiled hydrogel-based yarn muscles - Xinghao Hu; Jinchang Jiang; Hailong Wei; Jiayu Chen; Zhanyuan Wang; Ghassen Mhenni; Hong Li; Hongwei Hu; Shengping Dai; Shi Hyeong Kim; Jianning Ding (Chemical Engineering Journal, 2025)

Single-Neuron Reconstruction of the Macaque Primary Motor Cortex Reveals the Diversity of Neuronal Morphology - Siyu Li; Yan Shen; Yefei Chen; Zexuan Hong; Lewei Zhang; Lufeng Ding; Chao-Yu Yang; Xiaoyang Qi; Quqing Shen; Yanyang Xiao; Pak-Ming Lau; Zhonghua Lu; et al. (Neuroscience Bulletin, 2025)

Transcriptomic Analysis of Endocrine System Responses in Zebrafish Embryos Following Exposure to Environmentally Relevant Concentrations of Arsenate - Tao Li; Di Zhang; Liang Ding; Hongyan Zhou; Yizhong Hou; Huachang Hong; Hongjie Sun; Xinwei Yu (Fishes, 2025)
Water environments contaminated with arsenic (As) have become a significant environmental concern. Previous research has highlighted the detrimental effects of As on fish, but limited knowledge exists regarding its impacts on endocrine systems. To address this gap, zebrafish embryos were exposed to various concentrations (0, 25, 50, 75, and 150 μg/L) of arsenate (AsV) for 120 h post-fertilization (hpf). Our findings indicate that exposure to AsV significantly increases cortisol- and thyroid-stimulating hormone (TSH) levels while decreasing estradiol (E2) and testosterone (T) levels. Additionally, it initially decreases and then increases thyroxine (T4) contents. Furthermore, several key genes relevant to these endocrine systems also show significant influences. The results from principal component analysis demonstrate that TRH, TSH, TRHRb, and TRβ primarily affect the level of T4 while Cyp11b, StAR, hmgrb MC2R, and GR mainly influence cortisol levels. On the other hand, Cyp19a, Cyp17, 17βhsd, ERβ, LHR, hmgrb, and AR predominantly impact E2 and T levels. Transcriptomics and enrichment analysis reveal that these pathways are primarily associated with steroid hormone synthesis and transport. Furthermore, it was found that AsV stimulates the cAMP signaling pathway through a compensation mechanism. These results suggest that AsV may potentially act as environmental endocrine-disrupting chemicals with non-negligible interference effects on the endocrine system in zebrafish. This study holds theoretical value in assessing the environmental risk posed by As overall as well as providing an important basis for addressing human health issues and implementing preventive measures.

Liver transcriptome analysis reveals the molecular response to hibernation challenge in the Chinese soft-shelled turtle (Pelodiscus sinensis) - Muhammad Shahid Iqbal; Xiaoqi Ai; Qingjun Zhu; Ijaz Khan; Zeeshan Ali; Tian Lan; Li Ding; Meiling Hong (Frontiers in Marine Science, 2025)
Hibernation is a physiological strategy animals use to survive in hostile environments with extreme temperature challenges and food scarcity. During this state, significant changes occur in metabolism and cellular function, with numerous stress response pathways recalibrated to survive physiological challenges that could otherwise be fatal. Numerous studies were performed to explain the molecular mechanisms of mammalian hibernation, but detailed analyses remain scarce in reptiles. Given the limited understanding of the mechanisms regulating hibernation, we performed a comprehensive analysis of liver gene expression in the Chinese softshell turtle ( Pelodiscus sinensis ) comparing summer active (SA), hibernation (H), and early arousal (EA) states using RNA-sequencing. A total of 435 million high-quality reads were generated, identifying 3,508, 3,607, and 2,993 differentially expressed genes (DEGs) in the SA vs. H, H vs. EA, and EA vs. SA respectively. Gene ontology analysis revealed a shift in metabolic fuel utilization, with the down-regulation of metabolic and cellular processes during hibernation, reflecting a conserved strategy for energy conservation. The transition from hibernation to early arousal was marked by up-regulation of immune-related genes (e.g., CXCL12, ITGA4, PIGR) and endocrine regulators (e.g., CDKN1A, DLL4, IGF1R), facilitating metabolic recovery and cellular protection. Besides, we observed dynamic changes in carbohydrate and lipid metabolism, with down-regulation of hexokinase 2 (HK2) and glucose transporters during hibernation, and up-regulation of lipid metabolism genes (LSS, GPLD1) to support membrane integrity and signaling. Our findings provide insights into the molecular mechanisms underlying hibernation and arousal in ectotherms, with implications for understanding metabolic adaptations, immune regulation, and stress responses in extreme conditions.

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Thiophene and acetylene functionalized conjugated organic polymers with hollow nanotube structure toward high-performance photocatalytic H2O2 production - Yuntong Li; Boxuan Ding; Yan Sui; Wentong Chen; Dongsheng Liu; Wei Huang; Xiaodan Li; Wei Wang; Hong Zhong; Cheng Liu (Journal of Environmental Chemical Engineering, 2025)

Molecular mechanism of pyrazosulfuron-ethyl degradation by Chenggangzhangalella sp. BI-1 and study on enhanced bioremediation of contaminated soil with rhammelolipid - Hao Zhang; Zi-wei Hua; Zi-yue Ding; Hui-ying Yang; Tie-jun Wang; Yu-ying Li; B. Larry Li; Xing Huang; Peng-fei Duan; Qiu-hong Niu (Journal of Environmental Chemical Engineering, 2025)

Impacts of continuous potato cropping on soil microbial assembly processes and spread of potato common scab - Lichun Wang; Song Liu; Guokui Tian; Yang Pan; Haiyan Wang; Guangwei Qiu; Fengyun Li; Ze Pang; Kaixin Ding; Jinpeng Zhang; Hong Xue; Xinyuan Li; et al. (Applied Soil Ecology, 2025)

Z/E configuration controlled by a Taxus sesquiterpene synthase facilitating the biosynthesis of (3Z,6E)-α-farnesene - Xue Tang; Xian-Jing Zhang; Jing-Feng Pan; Kai Guo; Chun-Lin Tan; Qiao-Zhuo Zhang; Li-Ping Long; Rui-Feng Ding; Xue-Mei Niu; Yan Liu; Sheng-Hong Li (Phytochemistry, 2025)

The criticality of exports sophistication and CO2 emissions: A new path towards sustainable environmental management - Hong Yao; Hongjie Ding; Zheng Li; Ayza Shoukat (Journal of Environmental Management, 2025)

Zein film loaded with Fructus Ligustri Lucidi essential oil: Preparation, characterization and application in fresh-cut apple preservation - Hong Chen; Chengyan Yang; Xiangxun Zhuansun; Yao Li; Rui Han; Longgang Wang; Shengqing Ding; Qi Liu (Food Control, 2025)

Mechanism, diffusion, and kinetics characteristics of nitrocellulose denitrification revealed by DFT and MD - Shen Li; Zhong-Xin Liu; Shi-Ying Li; Ya-Jun Ding; Zhong-Liang Xiao; Jie Zhou; Xiao-Qing Wu; Hong-Lei Fan; Zheng-Hong Luo; Xi-Bao Zhang (Chemical Engineering Journal, 2025)

Chronic polyaluminum chloride perturbation shaped community assembly patterns: An overlooked mechanism of nitrogen removal inhibition - Nan-ping Wu; Qian Zhang; Hong-yu Wang; Yun-jie Zhang; Meng Li; Bin Ji; Yufei Bao; Bing Lin; Yu-wei Ding; Qi He; Jia-jing Chen (Chemical Engineering Journal, 2025)

Aldehyde-functionalization of chitin nanocrystals via SI-ARGET ATRP of lignin-derived monomers - Tongjun Yang; Rongli Li; Mingtao Ding; Hong Yu; Lihua Zhang; Haibo Xie (Carbohydrate Polymers, 2025)

Pyridoxine supplementation before puberty ameliorates MAM-induced cognitive and sensorimotor gating impairments - Cheng Xue; Xiao-Hui Li; Hong-Qun Ding; Xin Qian; Meng-Yu Zhang; Kai Chen; Zi-Wei Wei; Ying Li; Jun-Hai Jia; Wei-Ning Zhang (Metabolic Brain Disease, 2024)

Potassium status and the risk of type 2 diabetes, cardiovascular diseases, and mortality: a meta-analysis of prospective observational studies - Yahui Fan; Min Wu; Lu Ding; Huixin Ji; Jinping Zhao; Xiaohui Li; Zhaofang Li; Sijiao Liu; Hong Jiang; Jia Shi; Haoyuan Lei; Mingxu Wang; et al. (Critical Reviews in Food Science and Nutrition, 2024)

Recent advances in the influences of drying technologies on physicochemical properties and biological activities of plant polysaccharides - Huan Guo; Hong-Yan Liu; Hang Li; Ding-Tao Wu; Linda L. D. Zhong; Ren-You Gan; Hong Gao (Critical Reviews in Food Science and Nutrition, 2024)

Long-term straw return increases fungal residual contribution to soil microaggregate nitrogen pool: An eco-enzymatic stoichiometric study - Lei Xu; Yan Zhou; Congrong Miao; Hong Chen; Jianwei Zhang; Haoyu Qian; Pengfu Hou; Yanfeng Ding; Zhenghui Liu; Weiwei Li; Songhan Wang; Yu Jiang; et al. (Soil and Tillage Research, 2024)

Research on antibiotic resistance genes in wild and artificially bred green turtles (Chelonia mydas) - Xin Niu; Liu Lin; Ting Zhang; Xiaoyu An; Yupei Li; Yangfei Yu; Meiling Hong; Haitao Shi; Li Ding (Science of The Total Environment, 2024)

Insights into pore structure-activity relationships of iron catalysts supported on fluorine–cerium nanosheets for heterogeneous Fenton oxidation - Jing Lv; Hui Ye; Shurui Han; Jinli Zhao; Guodong Yang; Han Zhang; Xiaojian Fu; Jing Zhang; Qingping Xin; Lizhi Zhao; Hong Li; Ligang Lin; et al. (Journal of Environmental Chemical Engineering, 2024)

Mechanism of membrane fouling mitigation by microalgae biofilm formation for low C/N mariculture wastewater treatment: EPS characteristics, composition and interfacial interaction energy - Yanbo Liu; Jing Zhu; Weirun Li; Binghan Xie; Guoyu Zhang; Yi Ding; Feng Liu; Haili Tan; Yuhong Jia; Hong You; Zhipeng Li (Journal of Environmental Chemical Engineering, 2024)

Electricity production and nutrient recovery from waste activated sludge via microbial fuel cell and subsequent struvite crystallization: Effect of low temperature thermo-alkaline pretreatment - Lin Wei; Ziyue Li; Tianqiu Hong; Qiang Zhang; Lei Luo; Yiming Tang; Junjie Ji; Jianyu Kong; Xiaoke Ding (Bioresource Technology, 2024)

Serum soluble interleukin-2 receptor alpha may predict tubulointerstitial inflammatory cell infiltration and short-term disease progression in immunoglobin A nephropathy - Chenqi Xu; Kunming Pan; Jie Li; Yang Li; Shi Jin; Yiqin Shi; Jie Teng; Xiaoqiang Ding; Xialian Xu; Hong Liu (Immunologic Research, 2024)

Interactions between dissolved organic matter with different molecular weights and nonylphenol in surface water bodies - Demin Li; Zhaoyang Wang; Qianqian Ding; Hong Sun; Shuai Fang; Kangyi Zhang; Wenyi Hu; Jin Bian (Chemosphere, 2024)

JAK/STAT signaling pathway is involved in antibacterial immunity in the green peach aphid Myzus persicae (Sulzer) - Bo Ding; Chao Zhang; Li He; Qinghui Zeng; Senwen Zhang; Hanzhi Yang; Hong Yang (Pesticide Biochemistry and Physiology, 2024)

Experimental, theoretical and optimization studies on multimode vibration reduction of floating raft system based on NES cells - Hong-Li Wang; Meng Li; You-Cheng Zeng; Hu Ding (Ocean Engineering, 2024)

Lateral transport facilitates terrestrial organic carbon burial in the Santa Barbara Basin over the past 80 years (1937–2018 CE) - Hanyue Xu; Da-Wei Li; Hong-Chun Li; William M. Berelson; Yang Ding; Li Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

High mobility emissive BN-Embedded Dinaphthalenyl anthracene for organic light emitting transistors - Ze-Wei Lin; Pu Wang; Sheng-Hong Zhao; Yun-Tao Ding; Huanli Dong; Hao-Li Zhang (Chemical Engineering Journal, 2024)

Fabrication of thermo-responsive microcapsule pesticide delivery system from maleic anhydride-functionalized cellulose nanocrystals-stabilized pickering emulsion template - Jun Li; Chao Wu; Hong-jun Xu; Jia-wei Ding; Yong-jiang Li; Hui Jiang; Hui-fen Su; Sheng Chen; Xin Li; Muhammad Asif Javaid; De-qiang Li (Carbohydrate Polymers, 2024)

Identification of autophagy-related signatures in doxorubicin-induced cardiotoxicity - Haiyan Wu; Haoqiang Chen; Xiaoxue Ding; Xiaohui Kuang; Mingjie Pang; Suijuan Liu; Yan Zhang; Qian Wang; Kunzhi Li; Hong Zhang (Toxicology and Applied Pharmacology, 2024)

How to make lunar soil suitable for cultivation? – A review - Jinghang Ding; Yuxuan Xu; Jungang Tan; Hong Zhang; Xin Xiong; Chuang Mei; Mingjie Li; Gengxin Xie (Science of The Total Environment, 2024)

Holocene dynamics of the Indian summer monsoon inferred from a high-resolution peat α-cellulose δ18O record on the Tibetan Plateau - Jie Wang; Haijun Peng; Masao Uchida; Hongyan Zhao; Hanwei Ding; Hu Yao; Zehai Li; Bing Hong; Yetang Hong (Quaternary Science Reviews, 2024)

Mesoscopic influence mechanism of particle fragmentation on compressive deformation of gangue aggregates with different gradations under load - Laiwei Wu; Junmeng Li; Yanli Huang; Peng Huang; Changde Yang; Zizhao Ding; Hong Yu (Minerals Engineering, 2024)

Insight into electricity production performance from dried waste activated sludge in dual chamber microbial fuel cells: Influencing factors, neural network modelling and microbial community analysis - Lin Wei; Ziyue Li; Tianqiu Hong; Yiming Tang; Ying Ge; Dongdong Ji; Qiang Zhang; Lei Luo; Jianyu Kong; Xiaoke Ding (Journal of Environmental Chemical Engineering, 2024)

Insight into saffron associated microbiota from different origins and explore the endophytes for enhancement of bioactive compounds - Sirui Xu; Liang Hong; Tong Wu; Xinting Liu; Zihan Ding; Li Liu; Qingsong Shao; Ying Zheng; Bingcong Xing (Food Chemistry, 2024)

Discovery of anti-melanogenic components in persimmon (Diospyros kaki) leaf using LC-MS/MS-MN, AlphaFold2-enabled virtual screening and biological validation - Jiazheng Liu; Ting Xu; Jianjun Ding; Haoyue Wen; Jieru Meng; Qing Liu; Xiaomei Liu; Wei Zhang; Guo-Yuan Zhu; Zhi-Hong Jiang; Jin Gao; Li-Ping Bai (Food Chemistry, 2024)

Synthesis and fabrication of magnetically separable phosphate-modified magnetic chitosan composites for lead(II) selective removal from wastewater - Yaoyao Huang; Yuqi Peng; Guizhi Zhang; Zhengsijia Wu; Juan Li; Wei Ding; Hong Li; Yanyan An; Liang Ao; Yu Shen; Huaili Zheng (Environmental Research, 2024)

Synthesis and evaluation of a novel ternary quaternary ammonium salts-fluorescent template copolymer: Integrating flocculation, sterilization, and monitoring functions - Junyi Jiang; Xiaobo Tan; Manli Sun; Yaoyao Huang; Xincheng Jiang; Wei Ding; Hong Li; Huaili Zheng (Chemical Engineering Journal, 2024)

The LINGO-1-deficient neural stem cell-derived neural tissueoid showed enhanced retention and neuronal relay in the transected spinal cord - Ge Li; Li-Jun Huang; Bao Zhang; Shu Liu; Jing-Hua Liang; Ying Ding; Xiang Zeng; Bi-Qin Lai; Yuan-Huan Ma; Ya-Qiong Wang; Rui Wang; Hong-Bo Zhang; et al. (Chemical Engineering Journal, 2024)

Incorporating hydrogen bonding networks in microporous polymer membranes for high-flux hydrocarbon separation - Yanxiong Ren; Jingqi Fu; Rui Ding; Yunshu Li; Xu Liang; Zheyuan Guo; Jianyu Wang; Ziting Zhu; Hong Wu; Guangwei He; Zhongyi Jiang (Chemical Engineering Journal, 2024)

Novel avenues for achieving simultaneous high-efficiency oil removal and sterilization: Designing a quaternary ammonium-hydrophobic ternary template copolymer - Junyi Jiang; Xiaobo Tan; Zhanmei Zhang; Wei Ding; Manli Sun; Hong Li; Huaili Zheng (Chemical Engineering Journal, 2024)

Theoretical study of the reaction of organic peroxyl radicals with alkenes and their accretion products involved in the atmospheric nucleation - Biao Dong; Hong Ding; Huidi Zhang; Hu Zhao; Haojie Xu; Zhenyu Xu; Juanbao Wang; Yunfeng Li; Xiangli Shi (Atmospheric Environment, 2024)

Safety, pharmacokinetics, and food-effect of pivmecillinam after single- and multiple-dose in healthy Chinese subjects: a phase I study - Lu-Lu Zhang; Yi Liu; Qiong-Ye Huang; Hong-Wen Zhang; Li-Jun Xie; Juan Chen; Li Ding; Chen Zhou; Lu-Ning Sun; Yong-Qing Wang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Semi-synthesis and in vitro anti-cancer effects evaluation of novel xanthohumol derivatives - Xiaolong Sun; Jie Chen; Di Huang; Feng Ding; Long Zhao; Hong-Mei Li; Xiang-Shu Wang; Yu-Xin Zhang; Cheng-Zhu Wu (Molecular Diversity, 2024)

Global risk dynamics of Borrelia miyamotoi in the context of climate change - Tian Tang; Hong‐Han Ge; Tian Ma; Meng‐meng Hao; Shuai Chen; Chen‐Long Lv; Yun‐Bo Qiu; Yan‐He Wang; Yao Tian; Jin‐Jin Chen; Shuai Yuan; Qian Wang; et al. (Environmental Microbiology, 2024)
The impact of Borrelia miyamotoi on human health, facilitated by the expanding geographical distribution and increasing population of Ixodes ticks, remains obscure in the context of global climate change. We employed multiple models to evaluate the effect of global climate change on the risk of B. miyamotoi worldwide across various scenarios. The habitat suitability index of four primary vector tick species for B. miyamotoi , including Ixodes persulcatus , Ixodes ricinus, Ixodes pacificus and Ixodes scapularis , was projected using a boosted regression tree model, considering multiple shared socio‐economic pathway scenarios over various time periods. The modelling analysis reveals that, apart from I. scapularis , future global warming will result in a northward shift in the other three vector tick species and a gradual reduction in suitable habitats. Random forest models indicate consistent changes in B. miyamotoi and its primary tick species, with potential risk areas shrinking and shifting northward, particularly in the eastern USA, northeastern and northern Europe and northeast Asia. These findings highlight the urgent need for enhanced active surveillance of B. miyamotoi infection in primary vector tick species across projected potential risk areas. The effect of climate change on B. miyamotoi distribution might have significant implications for public health decision‐making regarding tick‐borne pathogens.

Multi-constraint improved RS path planning method for unmanned rice direct seeding machine - Lian Hu; Kang Hou; Jie He; Zhongxian Man; Jiasheng Xie; Pei Wang; Tuanpeng Tu; Ruitao Gao; Le Zi; Yufeng Huang; Mingjin Li; Shuaiqi Ding; et al. (Computers and Electronics in Agriculture, 2024)

Megastigmane glycosides from the traditional Uighur medicine Cydonia oblonga Mill. - Shan-Shan Jiao; Rui-Feng Ding; Xin Yuan; Xiao-Ping He; Yan Liu; Kai Guo; Sheng-Hong Li (Phytochemistry, 2024)

Synthesis of Cu/Mn bimetallic organic framework material and their catalytic performance for NH3-SCR - Wei Dong; Fuping Qian; Shian Zhou; Shenghua Wu; Qingda Gao; Tiejun Chun; Lei Ding; Hong-ming Long; Gang Li; Naijin Huang (Journal of Cleaner Production, 2024)

In situ desulfurization mechanism of molten salt thermal treatment for waste tires - Qiang Gao; Hongyun Hu; Chan Zou; Yan Ding; Chao He; Xian Li; Hong Yao (Fuel, 2024)

UVA light assisted activation of sulfite by metal–organic framework-derived FeOx@C catalyst for organic degradation: Formation and role of non-radical species - Hejiao Zhang; Shuang Liu; Wei Ding; Chao Liu; Yaoyao Huang; Hong Li; Huaili Zheng (Chemical Engineering Journal, 2024)

Synaptotagmin-1 antagonizes paraquat intracellular accumulation and nephrocyte toxicity by up-regulating SERBP1/GLUT2 expression - Ran Yin; Jingjing Ke; Mingming Zhao; Yitian Ding; Wenwen Li; Mengxuan Li; Lufeng Hu; Xiaoqin Dai; Guangliang Hong (Chemico-Biological Interactions, 2024)

Hipposponols A and B, two new 9, 11-secosterols from the marine sponge Hippospongia lachne de Laubenfels - Ya-Fang Ding; Li-Yun Liu; Jie Tang; Dong-Xue Fan; Yuan-Yuan Ji; Hou-Wen Lin; Jie Wang; Li-Li Hong (Natural Product Research, 2024)

Safety and environmental protection application of high performance solid waste unburned ceramsite and its lightweight high strength concrete - Kai-jing Tang; Hong-na An; Chuan-bei Liu; Ying-ding Li; Lu-jun Jia; Yun Tang; Qi-qiang Wang; Yong Jiang; Zi-jian Song (Sustainable Chemistry and Pharmacy, 2024)

The distinct spatiotemporal evolutionary landscape of HBV and HDV largely determines the unique epidemic features of HDV globally - Yibo Ding; Hongbo Guo; Xinfang Hong; Qiudi Li; Zhijiang Miao; Qiuwei Pan; Kuiyang Zheng; Wenshi Wang (Molecular Phylogenetics and Evolution, 2024)

Cretaceous-Cenozoic cooling history of central-northern Tibet: Insights from the fission track thermochronology of detrital apatite from sediments of the Tuotuohe Basin - Leyi Li; Hong Chang; Ruxin Ding; Xiaoke Qiang; Philippe Sorrel (Journal of Asian Earth Sciences, 2024)

Lateral holding behaviour of torpedo piles in spatially variable soil: Development of a probabilistic design approach - Jiang Tao Yi; Shi Jie Xu; Wu Hao Liu; Lin Ding; Zhen Wang; Hong Yu Tang; Xiao Bin Li (Computers and Geotechnics, 2024)

Prevalence and molecular characterization of Cryptosporidium spp., Enterocytozoon bieneusi, and Giardia duodenalis in dairy cattle in Ningxia, northwestern China - Ming-Yuan Wang; Shan Zhang; Zhan-Sheng Zhang; Xiao-Yin Qian; Hai-Liang Chai; Yan Wang; Wen-Jun Fan; Chao Yi; Yu-Lin Ding; Wen-Xiong Han; Li Zhao; Yong-Hong Liu (Veterinary Research Communications, 2024)

Dynamic intrauterine crosstalk promotes porcine embryo implantation during early pregnancy - Xupeng Zang; Shengchen Gu; Wenjing Wang; Junsong Shi; Jianyu Gan; Qun Hu; Chen Zhou; Yue Ding; Yanjuan He; Lei Jiang; Ting Gu; Zheng Xu; et al. (Science China Life Sciences, 2024)

Magnetized bentonite modified rice straw biochar: Qualitative and quantitative analysis of Cd(II) adsorption mechanism - Shu-zhi Liu; Wei Ding; Hong-wei Zhang; Zhu-shuai Li; Ke-chun Tian; Ce Liu; Zeng-chao Geng; Chen-yang Xu (Chemosphere, 2024)

Daphmacrimines A−K, Daphniphyllum alkaloids from Daphniphyllum macropodum Miq - Li-Li Xu; Zhen-Peng Niu; Duo-Zhi Chen; Yu Zhang; Qian Zhao; Hong Liang; Sheng Li; Jin-Liang Li; Xiao Ding; Chong-Lin Yang; Xiao-Jiang Hao (Phytochemistry, 2024)

Estimating soil salinity in mulched cotton fields using UAV-based hyperspectral remote sensing and a Seagull Optimization Algorithm-Enhanced Random Forest Model - Jiao Tan; Jianli Ding; Zeyuan Wang; Lijing Han; Xiao Wang; Yongkang Li; Zhe Zhang; Shanshan Meng; Weijian Cai; Yanhong Hong (Computers and Electronics in Agriculture, 2024)

Sulfonamide disinfection byproducts exhibited severe toxicity to human commensal bacteria - DongMing Cai; Jinjian Ding; Fangfang Li; Guoqiang Zhuang; Minjie Li; Liang-Hong Guo (Water Research, 2024)

Ergosterols with rare peroxide, oxetane ring moiety, and a lactone ring from Aspergillus spectabilis and their immunosuppressive activities - Mengsha Wei; Hong Liao; Qin Li; Xueying Deng; Chi Gao; Nanjin Ding; Weiguang Sun; Hucheng Zhu; Jieru Guo; Chunmei Chen; Yonghui Zhang (Phytochemistry, 2024)

α-Fe2O3 nanorods on CoFe-LDH@MX via interfacial interactions for Congo red removal: Experimental and mechanistic studies - Xianyong Hong; Mingxing Shi; Linrui Li; Zhoutian Ding; Zhiren Zhao; Ping Du; Mingzhu Xia; Fengyun Wang (Journal of Environmental Chemical Engineering, 2024)

Seasonal changes in hepatic lipid metabolism and apoptosis in Chinese soft-shelled turtle (Pelodiscus sinensis) - Xiaoqi Ai; Rui Lin; Zeeshan Ali; Qingjun Zhu; Li Ding; Haitao Shi; Meiling Hong (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Chemical constituents from the leaves of Fraxinus hubeiensis, an endemic plant from China - Li-Min Gong; Hong-Xia Tang; Ya-Jie Li; Rui-Ding Wen; Xin-Yi Liu; Yu-Wen Deng; Qing-Lai Wu; Zhi-Feng Zhang; Xu-Dong Zhou; Wei Wang (Biochemical Systematics and Ecology, 2024)

Genome-wide analysis of in vivo-evolved Candida auris reveals multidrug-resistance mechanisms - Xin-Fei Chen; Han Zhang; Ling-Li Liu; Li-Na Guo; Wen-Jing Liu; Ya-Li Liu; Ding-Ding Li; Ying Zhao; Ren-Yuan Zhu; Yi Li; Rong-Chen Dai; Shu-Ying Yu; et al. (Mycopathologia, 2024)

Analysis of morphology, histology characteristics, and circadian clock gene expression of Onychostoma macrolepis at the overwintering period and the breeding period - Yibin Ding; Jincan Li; Yao Gao; Xiaolin Wang; Yang Wang; Chao Zhu; Qimin Liu; Lijuan Zheng; Meng Qi; Lijun Zhang; Hong Ji; Fangxia Yang; et al. (Fish Physiology and Biochemistry, 2024)

Patient-derived pathogenic microbe deposition enhances exposure risk in pediatric clinics - Wan Wang; Zongyao Qiu; Hui Li; Xiaorong Wu; Ying Cui; Lixiang Xie; Bozhen Chang; Peipei Li; Hong Zeng; Tao Ding (Science of The Total Environment, 2024)

Sulfite induced degradation of sulfamethoxazole by a silica stabilized ZIF-67(Co) catalyst via non-radical pathways: Formation and role of high-valent Co(IV) and singlet oxygen - Shuang Liu; Chao Liu; Hejiao Zhang; Weizhen Zhang; Wei Ding; Huaili Zheng; Hong Li (Journal of Hazardous Materials, 2024)

Embryonic development and transcriptomic analysis in red-eared slider Trachemys scripta elegans under salinity stress - Jing Lin; Yuchen Kong; Haitao Shi; Meiling Hong; Li Ding (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Synergistic therapy for melanoma via bioactive compounds derived metal-phenolic networks - Zhenghao Zhou; Cong Li; Shuai Cui; Shian Sun; Shaowei Zhu; Qing Yu; Ning Ding; Hao Hong; Dongzhi Yang (Chemical Engineering Journal, 2024)

Chinese Society of Cardiology guidelines on the diagnosis and treatment of adult fulminant myocarditis - Jiangang Jiang; Hongyang Shu; Dao Wen Wang; Rutai Hui; Chenze Li; Xiao Ran; Hong Wang; Jing Zhang; Shaoping Nie; Guanglin Cui; Dingcheng Xiang; Qun Shao; et al. (Science China Life Sciences, 2024)

Integrated analysis of transcriptome and small RNAome reveals regulatory network of rapid and long-term response to heat stress in Rhododendron moulmainense - Si-Jia Liu; Chang Cai; Hong-Yue Cai; Yu-Qing Bai; Ding-Yue Wang; Hua Zhang; Jin-Gen Peng; Li-Juan Xie (Planta, 2024)
Main conclusion The post-transcriptional gene regulatory pathway and small RNA pathway play important roles in regulating the rapid and long-term response of Rhododendron moulmainense to high-temperature stress. Abstract The Rhododendron plays an important role in maintaining ecological balance. However, it is difficult to domesticate for use in urban ecosystems due to their strict optimum growth temperature condition, and its evolution and adaptation are little known. Here, we combined transcriptome and small RNAome to reveal the rapid response and long-term adaptability regulation strategies in Rhododendron moulmainense under high-temperature stress. The post-transcriptional gene regulatory pathway plays important roles in stress response, in which the protein folding pathway is rapidly induced at 4 h after heat stress, and alternative splicing plays an important role in regulating gene expression at 7 days after heat stress. The chloroplasts oxidative damage is the main factor inhibiting photosynthesis efficiency. Through WGCNA analysis, we identified gene association patterns and potential key regulatory genes responsible for maintaining the ROS steady-state under heat stress. Finally, we found that the sRNA synthesis pathway is induced under heat stress. Combined with small RNAome, we found that more miRNAs are significantly changed under long-term heat stress. Furthermore, MYBs might play a central role in target gene interaction network of differentially expressed miRNAs in R. moulmainense under heat stress. MYBs are closely related to ABA, consistently, ABA synthesis and signaling pathways are significantly inhibited, and the change in stomatal aperture is not obvious under heat stress. Taken together, we gained valuable insights into the transplantation and long-term conservation domestication of Rhododendron , and provide genetic resources for genetic modification and molecular breeding to improve heat resistance in Rhododendron .

Isolation and absolute configuration of alkylpyridine alkaloids from the marine sponge Hippospongia lachne - Dong-Xue Fan; Xiang-Chao Luo; Ya-Fang Ding; Li-Yun Liu; Xin Wang; Jia-Yan Pan; Yuan-Yuan Ji; Jie Wang; Cui Li; Li-Li Hong; Hou-Wen Lin (Phytochemistry, 2024)

Non-fitting functional representation for the equilibrium constant subject to reaction between H2S and CO2 - Chao-Wen Wang; Ji Li; Lie-Hui Zhang; Qun-Chao Ding; Guan-Hong Liu; Gao Li; Rui Jiang; Xiao-Long Peng; Lin-Sheng Wei; Hong-Ming Tang; Jian-Yi Liu; Chun-Sheng Jia (Fuel, 2024)

Quercetin analogs as α-glucosidase inhibitors with antidiabetic activity - Honghui Liu; Yan Wang; Jing Tong; Jing Li; Hong Ding (Food Bioscience, 2024)

Comparative toxic effect of ammonia exposure on Mauremys sinensis and invasive species Trachemys scripta elegans - Li Ding; Zubin Huang; Lingyue Liang; Haitao Shi; Zhenhua Fang; Meiling Hong (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Benthic foraminiferal assemblages in the coastal zone of the yellow river delta: Environmental significance and characteristics of microbial diversity - Shuyang Huang; Qing Li; Xiaohua Qiu; Hong You; Ruimin Lv; Wei Liu; Qingfeng Chen; Tiantian Wang; Jing Zhang; Junjian Ma; Zihao Wang; Shigang Ding (Continental Shelf Research, 2024)

Simultaneous adsorption of Ciprofloxacin and Ni(II) from wastewater using poly(vinyl alcohol)/poly(sodium-p-styrene-sulfonate) semi-interpenetrating polymer network@Ni foam: Insights into the synergistic and antagonistic mechanisms - Xincheng Jiang; Jiaxi Guo; Manli Sun; Qiang Sun; Wei Ding; Hong Li; Huaili Zheng (Chemical Engineering Journal, 2024)

Microparticle deposition induced asymmetric adhesive hydrogel for suture-less gastric trauma treatment - Lei Liang; Hongda Wang; Linfa Li; Ding Lin; Bingyan Guo; Mengmeng Yao; Zhijian Wei; Hong Zhang; Junjie Li (Chemical Engineering Journal, 2024)

Melting-salt crystallization assisted controllable synthesis of core-shell zeolite catalyst for effective coupling of microwave hotspot and catalytic active site - Kai Liu; Qiuyan Ding; Na Wang; Zongliang Kou; Anran Xu; Hong Li; Zhenyu Zhao; Yilai Jiao; Xin Gao (Chemical Engineering Journal, 2024)

Efficient degradation of imidacloprid by surface discharge cold plasma: Mechanism of interaction between ROS and molecular structure and evaluation of residual toxicity - Jia-Bao Ni; Xiao-Fang Jia; Jun-Ying Zhang; Chang-Jiang Ding; Wen-Li Tian; Wen-Jun Peng; Sara Zielinska; Hong-Wei Xiao; Xiao-Ming Fang (Journal of Hazardous Materials, 2024)

Cryoprotective effect of fistular onion stalk polysaccharide on frozen surimi derived from bighead carp: Physicochemical properties and gel quality during storage - Xiaoyue Sun; Qing Li; Ning Ding; Shijie Liang; Elliot Mubango; Yanyan Zheng; Qinye Yu; Ruitong Dai; Yuqing Tan; Yongkang Luo; Hui Hong (Food Hydrocolloids, 2024)

Effects of butyl paraben on behavior and molecular mechanism of Chinese striped-necked turtle (Mauremys sinensis) - Xia Wu; Ijaz Khan; Xiaoqi Ai; Jiliang Zhang; Haitao Shi; Ding Li; Meiling Hong (Aquatic Toxicology, 2024)

Enhanced Beta2-band Oscillations Denote Auditory Hallucination in Schizophrenia Patients and a Monkey Model of Psychosis - Shuo Ma; Tianzhen Chen; Wenjun Jia; Jie Liu; Shihan Ding; Puzhe Li; Hong Gan; Dapeng Zhang; Shuxin Shao; Mu-Ming Poo; Min Zhao; Bomin Sun; et al. (Neuroscience Bulletin, 2024)

Anti-CD20 treatment attenuates Th2 cell responses: implications for the role of lung follicular mature B cells in the asthmatic mice - Jilong He; Jingling Li; Qibin Lin; Haiyang Ni; Sisi Huang; Hong Cheng; Xuhong Ding; Yi Huang; Hongying Yu; Yaqing Xu; Hanxiang Nie (Inflammation Research, 2024)

Long-term straw returning improved soil nitrogen sequestration by accelerating the accumulation of amino acid nitrogen - Lei Xu; Hong Chen; Yan Zhou; Jianwei Zhang; Muhammad Yousaf Nadeem; Congrong Miao; Jiahui You; Weiwei Li; Yu Jiang; Yanfeng Ding; Ganghua Li (Agriculture, Ecosystems & Environment, 2024)

Seasonal variation, source apportionment, and cancer risk assessment of PM2.5-bound phthalates: a case study in Taiyuan, China - Wen-Jun Hong; Xun Wang; Jin-Jian Ding; Jian-Ming Jiang; Min-Jie Li; Shaoyang Ji; Nan Sang; Liang-Hong Guo (Air Quality, Atmosphere & Health, 2024)

A green synthesis route of cyclohexanol via transesterification reaction intensified by reactive distillation technology - Zhengkun Hou; Xueli Geng; Qiuyan Ding; Hong Li; Yaocong Guo; Ting Qiu; Chen Yang; Qinglian Wang; Xin Gao (Journal of Cleaner Production, 2024)

Tracing magmatic differentiation of peralkaline granites by using K stable isotopes - Hang Xu; Weiqiang Li; Xiao-Lei Wang; Jun Mu; De-Hong Du; Jiao-Long Zhao; Ding-Yi Xiong (Geochimica et Cosmochimica Acta, 2024)

Constructing mesoporous biochar derived from waste carton: Improving multi-site adsorption of dye wastewater and investigating mechanism - Yan-Shan Wang; Tong-Rong Huo; Yan Wang; Jia-Wen Bai; Ping-Ping Huang; Chen Li; Shi-Yu Deng; Hong Mei; Jun Qian; Xiao-Chi Zhang; Chen Ding; Qiu-Yu Zhang; et al. (Environmental Research, 2024)

Ultrathin RhCu bimetallenes for the selective electro-oxidation of glycerol - Qing-Ling Hong; Yue Zhao; Xuan Ai; Yu Ding; Fu-Min Li; Pei Chen; Pu-Jun Jin; Yu Chen (Chemical Engineering Journal, 2024)

Insight into the purification of arsenic-contaminated acid water by metal–organic framework MIL-53(Fe) with sulfite: The generation and effect of Fe(IV) - Liuwei Yang; Shuang Liu; Hejiao Zhang; Weizheng Zhang; Wei Ding; Huaili Zheng; Hong Li; Jun Zhai (Chemical Engineering Journal, 2024)

Overexpression of cucumber CYP82D47 enhances resistance to powdery mildew and Fusarium oxysporum f. sp. cucumerinum - Hong-yu Wang; Peng-fei Li; Yu Wang; Chun-yu Chi; Xiao-xia Jin; Guo-hua Ding (Functional & Integrative Genomics, 2024)

Morphological and transcriptomic analyses of embryonic development of red-eared slider Trachemys scripta elegans - Jing Lin; Miaomiao Zhang; Fangbin Liang; Yunfang Ni; Jiani Zhang; Haitao Shi; Meiling Hong; Li Ding (Animal Reproduction Science, 2024)

Mean annual precipitation modulates the assembly of high-affinity methanotroph communities and methane oxidation activity across grasslands - Chenxiao Ding; Yaowei Liu; Marc G. Dumont; Hong Pan; Kankan Zhao; Yuanheng Li; Qichun Zhang; Yu Luo; Shuo Jiao; Hongjie Di; Jianming Xu; Yong Li (Agriculture, Ecosystems & Environment, 2024)

Screening and expression analysis of genes related to skin coloration in pearlscale angelfish (Centropyge vrolikii) - Li-jun He; Zhen Yang; Zhao-wei Zhong; Yan Xu; Yan Feng; Zhen Ding; Hong-wei Liu; Yong-hua Jiang (Aquaculture International, 2024)

Associations of legacy perfluoroalkyl and polyfluoroalkyl substances, alternatives, and isomers with gestational diabetes mellitus and glucose homeostasis among women conceiving through assisted reproduction in Shanghai, China - Dandan Mao; Guodong Ding; Zixia Wang; Jiuru Zhao; Hong Li; Xiaoning Lei; Jiaqi Zheng; Yan Zhang; Rong Shi; Tao Yuan; Zhiwei Liu; Yu Gao; et al. (Environmental Science and Pollution Research, 2024)

Performance analysis of microbial fuel cell - membrane bioreactor with reduced graphene oxide enhanced polypyrrole conductive ceramic membrane: Wastewater treatment, membrane fouling and microbial community under high salinity - Rui Wang; Hong You; Binghan Xie; Guoyu Zhang; Jing Zhu; Weirun Li; Xinan Dong; Qiqing Qin; Mengying Wang; Yi Ding; Haili Tan; Yuhong Jia; et al. (Science of The Total Environment, 2024)

Study on the suppression characteristics and mechanism of ABC powder on pulverized coal explosion based on the analysis of thermal decomposition characteristics and reaction kinetics - Bingyou Jiang; Qi Yao; Mingqing Su; Jingjing Li; Kunlun Lu; Dawei Ding; Han Hong (Process Safety and Environmental Protection, 2024)

pH-responsive bentonite nanoclay carriers control the release of benzothiazolinone to restrain bacterial wilt disease - Liang Yang; Yao Wang; Yijia Liang; Haibin Deng; Jun Wang; Yuhao Dai; Fuyou Guo; Hong Zhou; Shili Li; Wei Ding (Pesticide Biochemistry and Physiology, 2024)

Cobalt(II) mediated calcium sulfite activation for efficient oxidative decontamination in waters: Performance, kinetics and mechanism - Bangkang Yue; Shuang Liu; Weizhen Zhang; Wei Ding; Huaili Zheng; Hong Li (Journal of Hazardous Materials, 2024)

Untargeted metabolomics analysis of non-volatile metabolites and dynamic changes of antioxidant capacity in Douchi with edible mushroom by-products - Pei-Xiu Rong; Xiao-Qin He; Mutamed Ayyash; Yi Liu; Ding-Tao Wu; Fang Geng; Hua-Bin Li; Siew Bee Ng; Hong-Yan Liu; Ren-You Gan (Food Chemistry, 2024)

Geographical distribution and potential distribution prediction of thirteen species of Citrus L. in China - Zhenhai Huang; Zexi Li; Lewen Yao; Yanghe Yuan; Zhengyi Hong; Shiyuan Huang; Ying Wang; Jianhao Ye; Lanyue Zhang; Jinlong Ding (Environmental Science and Pollution Research, 2023)

Projecting spatiotemporal dynamics of severe fever with thrombocytopenia syndrome in the mainland of China - Fang‐Yu Ding; Hong‐Han Ge; Tian Ma; Qian Wang; Meng‐Meng Hao; Hao Li; Xiao‐Ai Zhang; Richard James Maude; Li‐Ping Wang; Dong Jiang; Li‐Qun Fang; Wei Liu (Global Change Biology, 2023)
Severe fever with thrombocytopenia syndrome (SFTS) is an emerging infectious disease with increasing incidence and geographic extent. The extent to which global climate change affects the incidence of SFTS disease remains obscure. We use an integrated multi‐model, multi‐scenario framework to assess the impact of global climate change on SFTS disease in China. The spatial distribution of habitat suitability for the tick Haemaphysalis longicornis was predicted by applying a boosted regression tree model under four alternative climate change scenarios (RCP2.6, RCP4.5, RCP6.0, and RCP8.5) for the periods 2030–2039, 2050–2059, and 2080–2089. We incorporate the SFTS cases in the mainland of China from 2010 to 2019 with environmental variables and the projected distribution of H. longicornis into a generalized additive model to explore the current and future spatiotemporal dynamics of SFTS. Our results demonstrate an expanded geographic distribution of H. longicornis toward Northern and Northwestern China, showing a more pronounced change under the RCP8.5 scenario. In contrast, the environmental suitability of H. longicornis is predicted to be reduced in Central and Eastern China. The SFTS incidence in three time periods (2030–2039, 2050–2059, and 2080–2089) is predicted to be increased as compared to the 2010s in the context of various RCPs. A heterogeneous trend across provinces, however, was observed, when an increased incidence in Liaoning and Shandong provinces, while decreased incidence in Henan province is predicted. Notably, we predict possible outbreaks in Xinjiang and Yunnan in the future, where only sporadic cases have been reported previously. These findings highlight the need for tick control and population awareness of SFTS in endemic regions, and enhanced monitoring in potential risk areas.

Vibration reduction of floating raft system based on nonlinear energy sinks - Hong-Li Wang; Hu Ding (Ocean Engineering, 2023)

Sulforaphane alleviates the meiosis defects induced by 3-nitropropionic acid in mouse oocytes - Wei-Jian Li; Xuan Zhang; Ming Shen; Hong-Lin Liu; Li-Ren Ding (Food and Chemical Toxicology, 2023)

Analysis of the spatial-temporal evolution of Green and low carbon utilization efficiency of agricultural land in China and its influencing factors under the goal of carbon neutralization - Jun Fu; Rui Ding; Yu-qi Zhu; Lin-yu Du; Si-wei Shen; Li-na Peng; Jian Zou; Yu-xuan Hong; Juan Liang; Ke-xin Wang; Wen-qian Xiao (Environmental Research, 2023)

Utilizing internal resonant scattering to improve photoluminescence energy outcoupling of CsPbBr3/Cs4PbBr6 perovskite phosphor - Zong-Tao Li; Bo-Jia Li; Jia-Sheng Li; Cun-Jiang Song; Xin-Rui Ding; Hai-Long Yuan; Bin-Hai Yu; Yong Tang; Jian-Zhen Ou; Romain Gautier; Hong-Lei Ji; Hao-Chung Kuo (Chemical Engineering Journal, 2023)

Heteropoly acid supported on hierarchical Y zeolite decorated SiC foam as the structured catalytic packing for reactive distillation synthesis of ethyl lactate - Qiuyan Ding; Hengyu Shen; Zongliang Kou; Hong Li; Xiaolei Fan; Xiaoxia Ou; Yilai Jiao; Xin Gao (Chemical Engineering Journal, 2023)

Efficient defluorination of perfluorooctanoic acid enabled by single-atom Cu/reduced graphene oxide electrocatalytic anode and peroxymonosulfate activation - Danhong Shen; Linyu Shen; Bihong Zhang; Minjie Li; Jinjian Ding; Liang-Hong Guo (Chemical Engineering Journal, 2023)

A dual-mode method for detection of miRNA based on the photoluminescence and resonance light scattering - Xiaokun Wen; Jia Hua; Yadan Ding; Zhipeng Li; Hancheng Zhu; Guorui Wang; Jun Li; Xia Hong (Analytica Chimica Acta, 2023)

Perturbation indicator for Hall effect thruster operating state based on statistical characteristics of breathing oscillation time scale signals - Jingjing Li; Liqiu Wei; Yanlin Hu; Huibin Lian; Liwei Zhou; Xingyu Liu; Tianyuan Ji; Liang Han; Yongfeng He; Hong Li; Yongjie Ding (Advances in Space Research, 2023)

Environmental exposure and ecological risk of perfluorinated substances (PFASs) in the Shaying River Basin, China - Ya-Hui Zhang; Ting-Ting Ding; Zi-Yan Huang; Hong-Yi Liang; Shi-Lin Du; Jin Zhang; Hui-Xian Li (Chemosphere, 2023)

Shear behavior of cylindrical pin-sleeve connectors of neighboring segments of immersed tunnels - Jiao-Long Zhang; Ding-Li Jin; Yong Yuan; Hong Chen; Zhi-Yuan Hu; Jun-Nan Qiu (Tunnelling and Underground Space Technology, 2023)

Temporal variations of mangrove-derived organic carbon storage in two tropical estuaries in Hainan, China since 1960 CE - Mengfan Chu; Julian P. Sachs; Peng Peng; Hong-Chun Li; Yang Ding; Li Li; Meixun Zhao (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Insights into the organic degradation by sulfite activation with a Fe3O4/g-C3N4 photocatalyst under visible LED: Transformation of SO4•− to 1O2 - Shuang Liu; Hong Wu; Huaili Zheng; Weizhen Zhang; Wei Ding; Hong Li; Chao Liu (Journal of Environmental Chemical Engineering, 2023)

Contaminant occurrence, water quality criteria and tiered ecological risk assessment in water: A case study of antifouling biocides in the Qiantang River and its estuary, Eastern China - Hai-Wei Luo; Jian-Ming Jiang; Xun Wang; Minjie Li; Jin-Jian Ding; Wen-Jun Hong; Liang-Hong Guo (Marine Pollution Bulletin, 2023)

Reduction potential of vehicular emission in Chengdu, China: A case study of COVID-19 - Xinping Yang; Hefeng Zhang; Wei Li; Hong Tian; Yongdong Wang; Jing Zhou; Ze Bao; Xiaorui Chen; Teng Xiao; Yunjing Wang; Mingliang Fu; Xian Wu; et al. (Urban Climate, 2023)

Corrigendum to “Maternal linuron exposure alters testicular development in male offspring rats at the whole genome level” [Toxicology 389 (2017) 13–20] - Jianwei Bai; Hua Han; Feng Wang; Liyu Su; Hongwei Ding; Xiyin Hu; Binli Hu; Hong Li; Wei Zheng; Yan Li (Toxicology, 2023)

Vegetation structural shift tells environmental changes on the Tibetan Plateau over 40 years - Yanfen Wang; Kai Xue; Ronghai Hu; Boyang Ding; Hong Zeng; Ruijin Li; Bin Xu; Zhe Pang; Xiaoning Song; Congjia Li; Jianqing Du; Xiuchun Yang; et al. (Science Bulletin, 2023)

From arc accretion to within-plate extension: Geochronology and geochemistry of the Neoproterozoic magmatism on the northern margin of the Yangtze Block - Yu Huang; Xiao-Lei Wang; Jun-Yong Li; Ru-Cao Li; De-Hong Du; Chang-Hong Jiang; Lin-Sen Li; Ning Ding (Precambrian Research, 2023)

Association of Blood Heavy Metal Exposure with Atherosclerotic Cardiovascular Disease (ASCVD) Among White Adults: Evidence from NHANES 1999–2018 - Kai Wang; Yukang Mao; Zheng Liu; Yansong Li; Zhongming Li; Yan Sun; Yinzhang Ding; Xianling Liu; Jian Hong; Di Xu; Jing Zhang (Biological Trace Element Research, 2023)

Diet-mediated metaorganismal relay biotransformation: health effects and pathways - Yanmin Li; Hong Cao; Xiaoqian Wang; Lichun Guo; Xiaoying Ding; Wei Zhao; Feng Zhang (Critical Reviews in Food Science and Nutrition, 2023)

Martynoside rescues 5-fluorouracil-impaired ribosome biogenesis by stabilizing RPL27A - Mengying Hong; Yushen Du; Dongdong Chen; Yuan Shi; Menglong Hu; Kejun Tang; Zhuping Hong; Xiangzhi Meng; Wan Xu; Gaoqi Wu; Yuanyuan Yao; Liubo Chen; et al. (Science Bulletin, 2023)

A study on the analysis of dynamical transmission behavior and mining key monitoring stations in PM and O3 networks in the Beijing-Tianjin-Hebei region of China - Xiaofei Shi; Bo Li; Donglei Fu; Jiao Bai; Stephen Dauda Yabo; Kun Wang; Xiaoxiao Gao; Jie Ding; Hong Qi (Environmental Research, 2023)

TiO2 nanoparticles affect spermatogenesis and adhesion junctions via the ROS-mediated mTOR signalling pathway in Eriocheir sinensis testes - Lan-Min Wang; Ke Jia; Zhen-Fang Li; Hong-Yu Qi; Ding-Xi Liu; Ya-Jing Liang; Shuang-Li Hao; Fu-Qing Tan; Wan-Xi Yang (Environmental Pollution, 2023)

Characterizing thermo-hydraulic behaviors of seasonally frozen loess via a combined opto-electronic sensing system: Field monitoring and assessment - Hong-Hu Zhu; Bing Wu; Ding-Feng Cao; Biao Li; Zhi Wen; Xi-Feng Liu; Bin Shi (Journal of Hydrology, 2023)

Kinetics and mechanisms of bacteria disinfection by performic acid in wastewater: In comparison with peracetic acid and sodium hypochlorite - Ning Ding; Ziwei Li; Lin Jiang; Hong Liu; Yanping Zhang; Yingxue Sun (Science of The Total Environment, 2023)

Stelleratenoids A−F, macrocyclic daphnane orthoesters with anti-HIV activity from the roots of Stellera chamaejasme L. - Kang Ding; Zi-Yao Wu; Nuan Zhang; Jun He; Fan Zhang; Jing-Jing Wu; Hong-Jin Bai; Wei-Ku Zhang; Lin Li; Jie-Kun Xu (Phytochemistry, 2023)

The characteristic evolution and formation mechanism of hybrid microalgae biofilm and its application in mariculture wastewater treatment - Yanbo Liu; Guoyu Zhang; Weirun Li; Yi Ding; Hong You; Jing Zhu; Haoran Leng; Chi Xu; Xiaodi Xing; Jingyue Xu; Zhipeng Li (Journal of Environmental Chemical Engineering, 2023)

Commensal Bacillus siamensis LF4 ameliorates β-conglycinin induced inflammation in intestinal epithelial cells of Lateolabrax maculatus - Zi-Yan Liu; Hong-Ling Yang; Xi-Yue Ding; Sha Li; Guo-He Cai; Ji-Dan Ye; Chun-Xiao Zhang; Yun-Zhang Sun (Fish & Shellfish Immunology, 2023)

NLRP7 participates in the human subcortical maternal complex and its variants cause female infertility characterized by early embryo arrest - Jian Han; Nana Zhang; Qiqi Cao; Xiaodan Shi; Congjing Wang; Ximan Rui; Jie Ding; Chun Zhao; Junqiang Zhang; Xiufeng Ling; Hong Li; Yichun Guan; et al. (Journal of Molecular Medicine, 2023)

Seasonal spermatogenesis in the red-eared slider (Trachemys scripta elegans): The roles of GnRH, actin cytoskeleton, and MAPK - Na Li; Wenzhuo Rao; Shiyu Dai; Muhammad Shahid Iqbal; Haitao Shi; Li Ding; Meiling Hong (Animal Reproduction Science, 2023)

Long-term fertilizer postponing increases soil carbon sequestration by changing microbial composition in paddy soils: A 13CO2 labelling and PLFA study - Yan Zhou; Jianwei Zhang; Lei Xu; CongShan Xu; Hong Chen; Congrong Miao; Weiwei Li; Yu Jiang; Yanfeng Ding; Zhenghui Liu; Ganghua Li (Soil Biology and Biochemistry, 2023)

A novel reduced graphene oxide/polypyrrole conductive ceramic membrane enhanced electric field membrane bioreactor: Mariculture wastewater treatment performance and membrane fouling mitigation - Rui Wang; Hong You; Zhipeng Li; Binghan Xie; Shaojie Qi; Jing Zhu; Qiqing Qin; Han Wang; Jinxu Sun; Yi Ding; Yuhong Jia; Feng Liu (Bioresource Technology, 2023)

Klotho improves cardiac fibrosis, inflammatory cytokines, ferroptosis, and oxidative stress in mice with myocardial infarction - Kai WANG; Zhongming LI; Yinzhang DING; Zheng LIU; Yansong LI; Xianling LIU; Yan SUN; Jian HONG; Wei ZHENG; Lijun QIAN; Di XU (Journal of Physiology and Biochemistry, 2023)

Phytochemical and chemotaxonomic investigations on the aerial parts of Cynanchum auriculatum Royle ex Wight - Yanling Xu; Chenyang Wu; Lu Wang; Shengbo Wu; Yueru Chen; Xiaoxue Ding; Lin Wang; Yi Yu; Weiming Du; Yuqing Zhang; Rachel Y.H. Yang; Jian Hong; et al. (Biochemical Systematics and Ecology, 2023)

Deciphering roles of microbiota in arsenic biotransformation from the earthworm gut and skin - Hong-Tao Wang; Zong-Zheng Liang; Jing Ding; Gang Li; Sheng-Lei Fu; Dong Zhu (Journal of Hazardous Materials, 2023)

Facile synthesis of acid catalyzed sulfonic acid-amide functionalized magnetic sodium alginate and its efficient adsorption for ciprofloxacin and moxifloxacin - Junyi Jiang; Xincheng Jiang; Yuhong Zou; Jun Zhai; Wei Ding; Hong Li; Huaili Zheng (Journal of Cleaner Production, 2023)

Compositional changes of CH, O, and N moieties in petroleum ether-extractable portions from the three-step mild degradation of Dongming lignite - Yan-Jun Li; Wei Zhao; Guang-Hui Liu; Hao-Dong An; Ya-Jun Ma; Yu-Hong Kang; Yong Gao; Ni Bai; Ding-Kai Wang; Xian-Yong Wei; Hong-Cun Bai (Fuel, 2023)

Influences of high hydrostatic pressure on structures and properties of mung bean starch and quality of cationic starch - Ning Wang; Ying Dong; Yangyong Dai; Hong Zhang; Hanxue Hou; Wentao Wang; Xiuzhen Ding; Hui Zhang; Cheng Li (Food Research International, 2023)

Evaluation the food safety of cultured fat via detection of residues of adipogenic differentiation cocktail in cultured fat with high performance liquid chromatography and enzyme-linked immunosorbent assay - Wen-Juan Song; Pei-Pei Liu; Chun-Bao Li; Hui- Xia Li; Shi- Jie Ding; Guang-Hong Zhou (Food Research International, 2023)

Self-powered wastewater purification and phosphorus recovery systems with novel self-filtering Al-air batteries - Xinyang Li; Yujie Zhou; Xiangyuan Ma; Xiangrui Ding; Siyuan Lai; Xinyu Li; Guicheng Liu; Peizhe Sun; Hong Yao (Chemical Engineering Journal, 2023)

The real-time detection of acupuncture-induced extracellular ATP mobilization in acupoints and exploration of its role in acupuncture analgesia - Wei-Min Zuo; Yu-Jia Li; Kai-Yu Cui; Dan Shen; Di Zhang; Ya-Wen Zheng; Meng Huang; Yong Wu; Xue-Yong Shen; Li-Na Wang; Guang-Hong Ding (Purinergic Signalling, 2023)

Exploring the potential anti-Alzheimer disease mechanisms of Alpiniae Oxyphyliae Fructus by network pharmacology study and molecular docking - Rong-Rong Zhen; Yan-Jie Qu; Li-Min Zhang; Chao Gu; Min-Rui Ding; Lei Chen; Xiao Peng; Bing Hu; Hong-Mei An (Metabolic Brain Disease, 2023)

Individual tree segmentation and biomass estimation based on UAV Digital aerial photograph - Zhao Sun; Yi-fu Wang; Zhi-dan Ding; Rui-ting Liang; Yun-hong Xie; Rui Li; Hao-wei Li; Lei Pan; Yu-jun Sun (Journal of Mountain Science, 2023)

Water quality criteria derivation and tiered ecological risk evaluation of antifouling biocides in marine environment - Hai-Wei Luo; Min Lin; Xin-Xin Bai; Bin Xu; Minjie Li; Jin-Jian Ding; Wen-Jun Hong; Liang-Hong Guo (Marine Pollution Bulletin, 2023)

Photocurable liquid crystal hydrogels with different chargeability and tunable viscoelasticity based on chitin whiskers - Jingsheng Chen; Zelin Zhu; Jiaqing Chen; Yiting Luo; Lin Li; Kun Liu; Shan Ding; Hong Li; Mingxian Liu; Changren Zhou; Binghong Luo (Carbohydrate Polymers, 2023)

Chemical constituents from the flowers of Cynanchum auriculatum Royle ex Wight - Xiaoxue Ding; Lu Wang; Yanling Xu; Shengnan Zheng; Shuang Wang; Lin Wang; Miao Qin; Shengbo Wu; Yi Yu; Jian Hong; Honglei Zhou; Lingchuan Xu; et al. (Biochemical Systematics and Ecology, 2023)

Different roles of primary and secondary sources in reducing PM2.5: Insights from molecular markers in Pearl River Delta, South China - Kong Yang; Duo-Hong Chen; Xiang Ding; Jun Li; Yu-Qing Zhang; Tao Zhang; Qiao-Yun Wang; Jun-Qi Wang; Qian Cheng; Hao Jiang; Ping Liu; Zi-Rui Wang; et al. (Atmospheric Environment, 2023)

Three-dimensional numerical study of cooling water discharge of Daya Bay Nuclear Power Plant in southern coast of China during summer - Bingxu Geng; Lingyan Lu; Qian Cao; Wen Zhou; Shiyu Li; Ding Wen; Man Hong (Frontiers in Marine Science, 2023)
The impact of thermal pollution caused by cooling water discharge of power plant on the surrounding marine ecology has been a hot issue in oceanographic research. To reveal the distribution pattern of cooling water discharge of Daya Bay Nuclear Power Plant in summer and the impact on the surrounding marine environment, this research established a high-resolution three-dimensional (3D) numerical model based on ECOMSED in the Daya Bay. The model results are consistent with the observations on the distribution of tide level and temperature. The simulated horizontal distribution of temperature rise is consistent with the distribution trend of remote sensing images. The study showed that the stratification of the Daya Bay water is stronger in summer. The cooling water mainly spreads in the surface layer, and the temperature rise in the bottom layer is not apparent. Quantitative analysis showed that around 18.8-21.6 km 2 of the area has 1°C surface temperature rises. The area of temperature rises that exceeds 2 °C is between 6.2 and 8.1 km 2 . The area of temperature rises that exceeds 4 °C is between no more than 1.2 km 2 . The area with a bottom temperature rises of 1 °C does not exceed 2.2 km 2 , and there is no area that has a bottom temperature rise over 1 °C. The tidal dynamics process influences on the dispersion of cooling water discharge from Daya Bay Nuclear Power Plant, where the influence is more significant in the spring tide period than in the neap tide period. Our findings are consistent with previous researches.

Charge instability of topological Fermi arcs in chiral crystal CoSi - Zhicheng Rao; Quanxin Hu; Shangjie Tian; Qing Qu; Congrun Chen; Shunye Gao; Zhenyu Yuan; Cenyao Tang; Wenhui Fan; Jierui Huang; Yaobo Huang; Li Wang; et al. (Science Bulletin, 2023)

Stilbenes with potent cytotoxicity from the seedcases of Paeonia suffruticosa Andrews - Meng-Yue Yang; Zhao-Xiang Shao; Yue-Tong Wang; Yong-Lian Hou; Ding-Kang Zhu; Sha Chen; Ya-Hui Zhang; Fei Cao; Yong-Kui Jing; Bin Lin; Zhan-Lin Li; Da-Hong Li; et al. (Phytochemistry, 2023)

Fungal polyketides from a rhizospheric soil-derived Penicillium sp. YUD17004 associated with Gastrodia elata - Hong-Tao Li; Rui-Ning Yang; Tao Liu; Fei Xie; Hao-Jie Duan; Dan-Dan Xia; Hao Zhou; Zhong-Tao Ding (Phytochemistry, 2023)

One pot synthesis of Cu–Ni–S@Ni foam for the simultaneous removal and detection of norfloxacin - Xincheng Jiang; Yanyan An; Yaoyao Huang; Wei Ding; Manli Sun; Hong Li; Huaili Zheng (Journal of Cleaner Production, 2023)

Effect of ammonia stress on AMPK regulating-carbohydrate and lipid metabolism in Chinese striped-neck turtle (Mauremys sinensis) - Ijaz Khan; Yingnan Lu; Na Li; Haitao Shi; Li Ding; Meiling Hong; Zhenhua Fang (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

Formation mechanism and metabolic pathways of photogranule in batch and continuous-flow mode under high salinity stress - Jing Zhu; Hong You; Zhipeng Li; Binghan Xie; Weirun Li; Shaojie Qi; Rui Wang; Hongying Chen; Binyu Ma; Yi Ding; Haili Tan; Feng Liu; et al. (Chemical Engineering Journal, 2023)

Research on time series InSAR monitoring method for multiple types of surface deformation in mining area - Ya-xing Li; Ke-ming Yang; Jian-hong Zhang; Zhi-xian Hou; Shuang Wang; Xin-ming Ding (Natural Hazards, 2022)

First report of Claviceps purpurea causing ergot disease on wheat (Triticum aestivum) in southwestern China - Mingliang Ding; Zhiqin Wang; Qi Fan; Hefa Liao; Kun Liu; Mingju Li; Zhanhong Ma; Hong Yu; Yuanbing Wang (Journal of Plant Pathology, 2022)

Model tests on horizontal load-bearing and deformation resistance capacities of pile-bucket foundation in soft seabed soil - Ben He; Zhi-ying Yuan; Zhen-qiang Jiang; Ding-yu Ni; Li Shi; Zong-hao Yuan; Hong-lei Sun (Marine Georesources & Geotechnology, 2022)

The full-length genome sequence of a novel amalgavirus in Lilium spp. in China - Yanyan Huo; Xiaoting Li; Jiale Zhou; Shengjie Lin; Jiahao Ding; Huan Liu; Jianglian Yu; Ni Hong; Guoping Wang; Fang Ding (Archives of Virology, 2022)

Molecular characterization of a novel botourmiavirus with inverted complementary termini from the rice blast fungus Magnaporthe oryzae isolate HF04 - Simnin Shuai; Hong Zheng; Hang Ding; Yao Wang; Jinzhe Li; Fuyu Liu; Fengying Liu; Hongliu An; Shouguo Fang; Songbai Zhang; Qingchao Deng (Archives of Virology, 2022)

Correction to: Exosome-Derived lncRNA NEAT1 Exacerbates Sepsis-Associated Encephalopathy by Promoting Ferroptosis Through Regulating miR-9-5p/ TFRC and GOT1 Axis - Xue-biao Wei; Wen-qiang Jiang; Ju-hao Zeng; Lin-qiang Huang; Hong-guang Ding; Yuan-wen Jing; Yong-li Han; Yi-chen Li; Sheng-long Chen (Molecular Neurobiology, 2022)

Chemical and biological diversity of new natural products from marine sponges: a review (2009–2018) - Li-Li Hong; Ya-Fang Ding; Wei Zhang; Hou-Wen Lin (Marine Life Science & Technology, 2022)
Marine sponges are productive sources of bioactive secondary metabolites with over 200 new compounds isolated each year, contributing 23% of approved marine drugs so far. This review describes statistical research, structural diversity, and pharmacological activity of sponge derived new natural products from 2009 to 2018. Approximately 2762 new metabolites have been reported from 180 genera of sponges this decade, of which the main structural types are alkaloids and terpenoids, accounting for 50% of the total. More than half of new molecules showed biological activities including cytotoxic, antibacterial, antifungal, antiviral, anti-inflammatory, antioxidant, enzyme inhibition, and antimalarial activities. As summarized in this review, macrolides and peptides had higher proportions of new bioactive compounds in new compounds than other chemical classes. Every chemical class displayed cytotoxicity as the dominant activity. Alkaloids were the major contributors to antibacterial, antifungal, and antioxidant activities while steroids were primarily responsible for pest resistance activity. Alkaloids, terpenoids, and steroids displayed the most diverse biological activities. The statistic research of new compounds by published year, chemical class, sponge taxonomy, and biological activity are presented. Structural novelty and significant bioactivities of some representative compounds are highlighted. Marine sponges are rich sources of novel bioactive compounds and serve as animal hosts for microorganisms, highlighting the undisputed potential of sponges in the marine drugs research and development.

Lelliottia steviae sp. nov. isolated from Stevia rebaudiana Bertoni - Jing Lin; Ke Huang; Jing-Yu Huang; Yuan-Ru Xiong; Meng-Meng Wei; Na Xiao; Jia Gao; Xuan-Kai Ding; Zi-Yang Ma; Jun-Hao Sang; Ling-Xian Kong; Zhi-Yun Hong; et al. (Archives of Microbiology, 2022)

Short-term effect of sulfur dioxide (SO2) change on the risk of tuberculosis outpatient visits in 16 cities of Anhui Province, China: the first multi-city study to explore differences in occupational patients - Xin-Qiang Wang; Jia-Wen Zhao; Kang-Di Zhang; Wen-Jie Yu; Jie Wang; Ying-Qing Li; Xin Cheng; Zhen-Hua Li; Yi-Cheng Mao; Cheng-Yang Hu; Kai Huang; Kun Ding; et al. (Environmental Science and Pollution Research, 2022)

Intelligent identification method and application of seismic faults based on a balanced classification network - Jing Yang; Ren-Wei Ding; Hui-Yong Wang; Nian-Tian Lin; Li-Hong Zhao; Shuo Zhao; Yu-Jie Zhang (Applied Geophysics, 2022)

MiR-1260b protects against LPS-induced degenerative changes in nucleus pulposus cells through targeting TCF7L2 - Shijie Chen; Guixia Shi; Jin Zeng; Ping Huang Li; Yi Peng; Zhiyu Ding; Hong Qing Cao; Ruping Zheng; Weiguo Wang (Human Cell, 2022)

Pathways of soil N2O uptake, consumption, and its driving factors: a review - Hongshan Liu; Yuefen Li; Baobao Pan; Xiangzhou Zheng; Juhua Yu; Hong Ding; Yushu Zhang (Environmental Science and Pollution Research, 2022)

Short-term effect of ambient air pollutant change on the risk of tuberculosis outpatient visits: a time-series study in Fuyang, China - Xin-Qiang Wang; Ying-Qing Li; Cheng-Yang Hu; Kai Huang; Kun Ding; Xiao-Jing Yang; Xin Cheng; Kang-Di Zhang; Wen-Jie Yu; Jie Wang; Yong-Zhong Zhang; Zhen-tao Ding; et al. (Environmental Science and Pollution Research, 2022)

Exosome-Derived lncRNA NEAT1 Exacerbates Sepsis-Associated Encephalopathy by Promoting Ferroptosis Through Regulating miR-9-5p/TFRC and GOT1 Axis - Xue-biao Wei; Wen-qiang Jiang; Ju-hao Zeng; Lin-qiang Huang; Hong-guang Ding; Yuan-wen Jing; Yong-li Han; Yi-chen Li; Sheng-long Chen (Molecular Neurobiology, 2022)
Sepsis can cause sepsis-associated encephalopathy (SAE), but whether SAE was induced or exacerbated by ferroptosis remains unknown. In this study, the rat sepsis model was constructed using the cecal ligation and puncture method. The blood–brain barrier (BBB) permeability was measured by Evans blue dye (EBD) in vivo. The levels of ROS, Fe ion, MDA, GSH, and GPX4 were assessed by enzyme-linked immunosorbent assay (ELISA). The exosomes isolated from serum were cultured with bEnd.3 cells for the in vitro analysis. Moreover, bEnd.3 cells cultured with 100 μM FeCl3 (iron-rich) were to simulate ferroptosis stress. The cell viability was evaluated by Cell Counting Kit-8 (CCK-8) assay. A dual-luciferase reporter gene assay was performed to confirm the relationship between miR-9-5p with NEAT1, TFRC , and GOT1 . In vivo, it is found that BBB permeability was damaged in model rats. Level of ROS, Fe ion, and MDA was increased, and level of GSH and GPX4 was decreased, which means ferroptosis was induced by sepsis. Exosome-packaged NEAT1 in serum was significantly upregulated in model rats. In vitro, it is found that NEAT1 functions as a ceRNA for miR-9-5p to facilitate TFRC and GOT1 expression. Overexpression of NEAT1 enhanced ferroptosis stress in bEnd.3 cells. Increased miR-9-5p alleviated sepsis-induced ferroptosis by suppressing the expression of TFRC and GOT1 both in vivo and in vitro. In conclusion, these findings suggest that sepsis induced high expression of serous exosome-derived NEAT1, and it might exacerbate SAE by promoting ferroptosis through regulating miR-9-5p/ TFRC and GOT1 axis.

Is Zooplankton Body Size an Indicator of Water Quality in (Sub)tropical Reservoirs in China? - Li Wang; Jun Chen; Haojie Su; Xufa Ma; Zhixu Wu; Hong Shen; Jia Yu; Jiarui Liu; Yao Wu; Guangyi Ding; Ping Xie (Ecosystems, 2022)

Sweet tea ( Lithocarpus polystachyus rehd.) as a new natural source of bioactive dihydrochalcones with multiple health benefits - Ao Shang; Hong-Yan Liu; Min Luo; Yu Xia; Xiao Yang; Hang-Yu Li; Ding-Tao Wu; Quancai Sun; Fang Geng; Ren-You Gan (Critical Reviews in Food Science and Nutrition, 2022)

Sex-specific mediation of placental inflammatory biomarkers in the effects of prenatal phthalate coexposure on preschooler cognitive development - Hui Gao; Juan Tong; Bei-bei Zhu; Meng-long Geng; Hong Gan; Li Sun; Xiao-yan Wu; Kun Huang; Hui Cao; Wen-wen Liu; Shu-man Tao; Peng Ding; et al. (Environmental Science and Pollution Research, 2022)

Numerical investigation of the control factors driving Zhe-Min Coastal Current - Yang Zhang; Fei Chai; Joseph Zhang; Yang Ding; Min Bao; Yunwei Yan; Hong Li; Wei Yu; Liang Chang (Acta Oceanologica Sinica, 2022)

Microbial controls on heavy metals and nutrients simultaneous release in a seasonally stratified reservoir - Xuecheng Zhang; Shiyuan Ding; Hong Lv; Gaoyang Cui; Mengdi Yang; Yiyao Wang; Tianhao Guan; Xiao-Dong Li (Environmental Science and Pollution Research, 2022)

External evaluation of published population pharmacokinetic models of polymyxin B - Ya-qian Li; Kai-feng Chen; Jun-jie Ding; Hong-yi Tan; Nan Yang; Ya-qi Lin; Cui-fang Wu; Yue-liang Xie; Guo-ping Yang; Jing-Jing Liu; Qi Pei (European Journal of Clinical Pharmacology, 2021)

Emerging role of air pollution in chronic kidney disease - Yue Chen; Fan Cao; Jian-Ping Xiao; Xin-Yu Fang; Xue-Rong Wang; Li-Hong Ding; De-Guang Wang; Hai-Feng Pan (Environmental Science and Pollution Research, 2021)

Retraction Note to: CiRS-126 inhibits proliferation of ovarian granulosa cells through targeting the miR-21-PDCD4-ROS axis in a polycystic ovarian syndrome model - Jiafeng Lu; Ying Xue; Yuhang Wang; Yang Ding; Qinyan Zou; Min Pan; Longwei Qiao; Chunhua Zhang; Qinyu Ge; Ting Wang; Hong Li (Cell and Tissue Research, 2021)

Shifting roles of the East China Sea in the phylogeography of red nanmu in East Asia - Kai Jiang; Xin Tong; Yan‐Qian Ding; Zheng‐Wei Wang; Li‐Yuan Miao; Yue‐E Xiao; Wei‐Chang Huang; Yong‐Hong Hu; Xiao‐Yong Chen (Journal of Biogeography, 2021)
Aim The effect of eustasy driven by climatic oscillations on species diversification across the East China Sea (ECS) remains unclear. In this study, Machilus thunbergii (红楠, red nanmu in Chinese) was used as a model species to determine whether the ECS acted as either a “species pump” or “species vacuum” during the Pleistocene. Locations Eastern China, and southern and central Japan. Taxon Lauraceae. Methods Ecological niche modelling was employed to predict the potential distribution of M . thunbergii during the Last Glacial Maximum (LGM) and the last interglacial period. Nuclear microsatellite and chloroplast markers were used to reveal the phylogeographic pattern and infer the population history of 33 M . thunbergii populations. Results The ecological niche models suggested that the ECS provided potentially suitable habitats for M. thunbergii during the LGM. A sharp change in cpDNA haplotypes was found along the eastern China coasts, while microsatellites revealed a clinal pattern for genetic composition from eastern China to central Japan. The divergent lineages formed an admixture on the Zhoushan Archipelago of China and Kyushu Island of Japan. The estimated divergent and admixture times were c . 68 kyr and c . 15 kyr, corresponding to the periods where there were rising sea levels after the MIS4 glaciation and falling sea levels during the LGM, respectively. Main conclusions Machilus thunbergii probably underwent alternating population isolation during interglacial periods and connection during glacial maxima across the ECS, but such periodicity of isolation and connection seems not to have promoted diversification as suggested by the species pump hypothesis. Incipient divergence has been periodically wiped out due to frequent coalescence, rendering the ECS more like a “species vacuum”, particularly for species with relatively long generation lengths.

Establishment and characterization of the Bactrocera dorsalis (Diptera: Tephritidae) embryonic cell line QAU-Bd-E-2 - Gui-Ling Zheng; Jie Li; Qian-Long Yu; Bin Zhang; Xue-Meng Ding; Hui Li; Hong-Xu Zhou; Fang-Hao Wan; Chang-You Li (In Vitro Cellular & Developmental Biology - Animal, 2021)

Transcriptome analysis of differentially expressed genes in chrysanthemum MET1 RNA interference lines - Dong-ru Kang; Yi Zhu; Shuai-lei Li; Peng-hui Ai; Muhammad Ayoub Khan; Hong-xu Ding; Ying Wang; Zi-cheng Wang (Physiology and Molecular Biology of Plants, 2021)

Individual variation in metabolic rate, locomotion capacity and hypoxia tolerance and their relationships in juveniles of three freshwater fish species - Xu Pang; De-Yong Pu; Dan-Yang Xia; Xiao-Hong Liu; Shi-Hua Ding; Yun Li; Shi-Jian Fu (Journal of Comparative Physiology B, 2021)

SR-B1 and CD10 combined immunoprofile for differential diagnosis of metastatic clear cell renal cell carcinoma and clear cell carcinoma of the ovary - Teng Jiang; Xiaoli Diao; Meili Ding; Xiao Niu; Chao Wang; Yan Qi; Wei Jia; Lijuan Pang; Wenhao Hu; Hong Zou; Feng Li (Journal of Molecular Histology, 2021)
Both clear cell renal carcinoma (ccRCC) and clear cell carcinoma of the ovary (CCOC) have a clear cytoplasmic morphological feature, hence it is difficult to identify metastatic ccRCC and CCOC by morphology alone. At present, there are no effective immunohistochemical markers to distinguish between these two tumors. Studies have shown that the clear cytoplasm of ccRCC is mainly caused by cholesterol-rich lipids in the cytoplasm, while that of CCOC is due to the accumulation of cytoplasmic glycogen. Objective: to hypothesize that the scavenger receptor class B-type 1 (SR-B1) protein responsible for HDL cholesterol uptake may be differentially expressed in ccRCC and CCOC, and high CD10 expression in the renal tubular epithelium may assist in distinguishing between ccRCC and CCOC. Methods: effective immunohistochemical markers were applied in 90 cases of renal clear cell carcinoma and 31 cases of ovarian cancer to distinguish between the two types of tumors.Result: SR-B1 and CD10 expression is significantly higher in ccRCC than CCOC. Both SR-B1 and CD10 exhibited focal weak-medium intensity staining in CCOC, and their staining extent and intensity were significantly lower than ccRCC. The sensitivity and specificity of SR-B1 for identifying ccRCC were 74.4% and 83.9%, respectively. The sensitivity and specificity of CD10 for identifying CCOC were 93.3% and 80.6%, respectively. The combined SR-B1( +) CD10( +) immunoprofile supports the diagnosis of ccRCC with a specificity of 93.5%. The combined SR-B1(-) CD10(-) immunoprofile supports the diagnosis of CCOC with a specificity of 93.3%. Conclusions: our findings demonstrate that the combination of SR-B1 and CD10 immunoprofiling is a valuable tool for differential diagnosis of ccRCC and CCOC.

Ground roll separation method via threshold filtering and constraint of seismic wavelet support in curvelet domain - De-ying Wang; Li-hua Chen; Lie-qian Dong; Li-hong Zhao; Ren-wei Ding; Cheng-zhen Ding (Applied Geophysics, 2021)

Lithological and environmental controls on large tafoni along conglomerate cliffs in subtropic humid Danxiashan UNESCO Global Geopark - Xin Chen; Liu-qin Chen; Yan-hong Zhang; Ding-ding Du; Hai-ping Hu; Dong-xing Liu; Wen-zhuo Li (Journal of Mountain Science, 2021)

Curcumin protects thymus against D-galactose-induced senescence in mice - Jie-han Li; Ting-ting Wei; Li Guo; Jia-hui Cao; Yuan-kang Feng; Shu-ning Guo; Guo-hong Liu; Yi Ding; Yu-rong Chai (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)

IbERF71, with IbMYB340 and IbbHLH2, coregulates anthocyanin accumulation by binding to the IbANS1 promoter in purple-fleshed sweet potato (Ipomoea batatas L.) - Zhiyuan Ning; Kangdi Hu; Zhilin Zhou; Donglan Zhao; Jun Tang; Hong Wang; Lixia Li; Chen Ding; Xiaoyan Chen; Gaifang Yao; Hua Zhang (Plant Cell Reports, 2021)

Field tests of micro screw anchor piles under different loading conditions at three soil sites - Shi-Jin Feng; Wen-Ding Fu; Hong-Xin Chen; Hong-Xing Li; Yan-Li Xie; Shao-Feng Lv; Jin Li (Bulletin of Engineering Geology and the Environment, 2021)

Artificial Neural Network-based prediction of glacial debris flows in the ParlungZangbo Basin, southeastern Tibetan Plateau, China - Wang Tang; Hai-tao Ding; Ning-sheng Chen; Shang-Chang Ma; Li-hong Liu; Kang-lin Wu; Shu-feng Tian (Journal of Mountain Science, 2021)

HuR Promotes Ovarian Cancer Cell Proliferation by Regulating TIMM44 mRNA Stability - Xiaohui Yu; Yujiao Li; Yumei Ding; Hong Zhang; Ning Ding; Ming Lu (Cell Biochemistry and Biophysics, 2020)

Larger regional volume of the thalamus in diarrhea-predominant irritable bowel syndrome: a cross-sectional study - Cui Ping Mao; Fen Rong Chen; Hong Hong Sun; Mei Juan Shi; Hua Juan Yang; Xiao Hui Li; Dun Ding (Brain Imaging and Behavior, 2020)

Influence of complex topography on magnetotelluric-observed data using three-dimensional numerical simulation: A case from Guangxi area, China - Xiong Bin; Luo Tian-Ya; Chen Long-Wei; Dai Shi-Kun; Xu Zhi-Feng; Li Chang-Wei; Ding Yan-Li; Wang Hong-Hua; Li Jing-He (Applied Geophysics, 2020)

The Phylogeny and Functional Characterization of Peanut Acyl-ACP Thioesterases - Zhenying Peng; Hui Zhang; Haiying Tian; Lei Shan; Zhimeng Zhang; Hong Ding; Wenwei Gao; Xinguo Li (Journal of Plant Growth Regulation, 2020)
Fatty acyl-acyl thioesterases (FATs), which hydrolyze the thioester bond linking acyl chains to an acyl carrier protein, thereby terminating their elongation, contribute significantly to the fatty acid (FA) content and composition of seed storage lipids. The peanut ( Arachis hypogaea L.) genome was found to harbor 21 FAT ( AhFAT ) genes, distributed over 12 of the 20 chromosomes. The length of their predicted translation products varied from 74 to 415 residues, and all but one included the 1–2 Acyl-ACP_TE conserved domains. All of the coding sequences were interrupted by at least one intron, with the exon number ranging from two to 12, and five of the genes were liable to alternative splicing. When the RNA-Seq platform was used to assess the transcriptional behavior of the 21 AhFAT genes, transcription of only 13 was detectable in samples of root, leaves, and developing seed; among these, six were transcribed throughout the plant, three were root-specific and one was leaf-specific. A detailed analysis of a pair of homologous AhFATs showed that the coding region of each was split into six exons and that both were transcribed in all of the plant organs surveyed (although the intensity of their transcription was not the same in immature seed). The product of both genes was deposited in the chloroplast outer membrane. The constitutive expression of these genes in either yeast or Arabidopsis thaliana increased the FA content, especially that of saturated FAs. In peanut genome, 21 AhFAT genes were found and two of them were transformed into yeast and Arabidopsis for function identification. Results showed that overexpression of these two genes could increase the FA content, especially the saturated FAs content.

Privet golden leaves adapt unexpectedly well to light changes - Ming Yuan; Bo Huang; Li-Hua Dong; Qiao-Hong Han; Yong Yang; Chun-Bang Ding; Chao Hu; Yang-Er Chen; Zhong-Wei Zhang; Shu Yuan (Horticulture, Environment, and Biotechnology, 2020)

Effects of an oasis protective system on aeolian sediment deposition: a case study from Gelintan oasis, southeastern edge of the Tengger Desert, China - Jing Ding; Yun-hu Xie; Xiao-jia Li; Hong-tao Jiang; Ji Wang; Xiao-xi Liu; Xue-qin Wu; Yu-hao Wang; Chun-xing Hai (Journal of Mountain Science, 2020)

Astrocytic GABAB Receptors in Mouse Hippocampus Control Responses to Behavioral Challenges through Astrocytic BDNF - Ji-Hong Liu; Ze-Lin Li; Yi-Si Liu; Huai-De Chu; Neng-Yuan Hu; Ding-Yu Wu; Lang Huang; Shu-Ji Li; Xiao-Wen Li; Jian-Ming Yang; Tian-Ming Gao (Neuroscience Bulletin, 2020)

RETRACTED ARTICLE: CiRS-126 inhibits proliferation of ovarian granulosa cells through targeting the miR-21-PDCD4-ROS axis in a polycystic ovarian syndrome model - Jiafeng Lu; Ying Xue; Yuhang Wang; Yang Ding; Qinyan Zou; Min Pan; Longwei Qiao; Chunhua Zhang; Qinyu Ge; Ting Wang; Hong Li (Cell and Tissue Research, 2020)

The Family of Peanut Fatty Acid Desaturase Genes and a Functional Analysis of Four ω-3 AhFAD3 Members - Zhenying Peng; Jian Ruan; Haiying Tian; Lei Shan; Jingjing Meng; Feng Guo; Zhimeng Zhang; Hong Ding; Shubo Wan; Xinguo Li (Plant Molecular Biology Reporter, 2020)
The synthesis of α-linolenic acid (ALA) requires the activity of ω-3 fatty acid desaturases (ω-3 FADs). The quality of peanut oil would be much improved if the content of ALA could be increased. A scan of the peanut genome revealed that it harbored 36 FAD genes, mapping to 16 of the species’ 20 chromosomes. A phylogenetic analysis concluded that these genes belonged to six sub-families, namely stearoyl-acyl-acyl carrier protein desaturases ( SAD ), FAD2 , FAD3 , FAD4/5 , FAD6 and FAD7/8 . Of these, FAD3 and FAD7/8 encoded ω-3 FADs, while genes belonging to the other four sub-families encoded ω-6 FADs. Based on RNA-Seq data, each of the 36 FAD genes was shown to be transcribed in non-stressed plants, but there was variation between them with respect to which organs they were transcribed in. Four ω-3 AhFAD3 genes were functionally characterized; when expressed in Arabidopsis thaliana protoplasts, each was localized mainly in the endoplasmic reticulum, while within peanut, the genes were more strongly transcribed in the developing seed than in either the root or the leaf. When constitutively expressed in Arabidopsis thaliana , both the total fatty acid content of the seed and the relative contribution of ALA were increased. The transgenic seedlings also exhibited an improved level of survival when challenged by salinity stress.

MicroRNA-625-5p Sponges lncRNA MALAT1 to Inhibit Cervical Carcinoma Cell Growth by Suppressing NF-κB Signaling - Yujiao Li; Yumei Ding; Ning Ding; Hong Zhang; Ming Lu; Xiaorong Cui; Xiaohui Yu (Cell Biochemistry and Biophysics, 2020)

RNA-Seq revealed that infection with white tip nematodes could downregulate rice photosynthetic genes - Hong-Le Wang; Si-Hua Yang; Mei Lv; Shan-Wen Ding; Jun-Yi Li; Chun-Ling Xu; Hui Xie (Functional & Integrative Genomics, 2020)

Synchrotron Radiation-Based Three-Dimensional Visualization of Angioarchitectural Remodeling in Hippocampus of Epileptic Rats - Pan Gu; Zi-Hao Xu; Yu-Ze Cao; Sheng-Hui Liao; Qian-Fang Deng; Xian-Zhen Yin; Zhuo-Lu Wang; Zhuo-Hui Chen; Xin-Hang Hu; Hui Wang; Li-Zhi Li; Shi-Xin Liu; et al. (Neuroscience Bulletin, 2020)

The acute effects of ultraviolet radiation exposure on solar dermatitis in Shanghai, China - Guojiang Zhou; Li Peng; Wei Gao; Ying Zou; Yimei Tan; Yangfeng Ding; Shanqun Li; Hong Sun; Renjie Chen (International Journal of Biometeorology, 2020)

Multicenter-Based Population Pharmacokinetic Analysis of Ciclosporin in Hematopoietic Stem Cell Transplantation Patients - Ling Xue; Wen-juan Zhang; Ji-xin Tian; Lin-na Liu; Hai-hong Yan; Wen-wen Zhang; Xiao-liang Ding; Jing-jing Zhang; Li-yan Miao (Pharmaceutical Research, 2020)

Effects of topography on dynamic responses of single piles under vertical cyclic loading - Li-ming Qu; Xuan-ming Ding; Chong-rong Wu; Yong-hong Long; Jin-chuan Yang (Journal of Mountain Science, 2020)

One bis-indole alkaloid-voacamine from Voacanga africana Stapf: biological activity evaluation of PTP1B in vitro utilizing enzymology method based on SPRi expriment - Yan-Qiu Wang; Hong-Xiang Li; Xiao-Chun Liu; Jin-Shuang Zhao; Rong-Qiang Liu; Wen-ying Huai; Wei-Jun Ding; Tian-E Zhang; Yun Deng (Natural Product Research, 2019)

Characterization of the immunological factors in turbot (Scophthalmus maximus) seminal plasma and their correlation with sperm quality - Ming Ming Han; Fu Hong Ding; Jun Li (Aquaculture International, 2019)

Wind and sand control by an oasis protective system: a case from the southeastern edge of the Tengger Desert, China - Yun-hu Xie; Xiao-hong Dang; Zhong-ju Meng; Hong-tao Jiang; Xiao-jia Li; Rui-ping Zhou; Dan-dan Zhou; Xiao-xi Liu; Jing Ding; Xue-qin Wu; Yu-hao Wang; Chun-xing Hai; et al. (Journal of Mountain Science, 2019)

Development, Optimization, and Evaluation In Vitro/In Vivo of Oral Liquid System for Synchronized Sustained Release of Levodopa/Benserazide - Yang Qu; Wen-Long Lai; Yuan-Rong Xin; Fei-Qin Zhu; Yuan Zhu; Li Wang; Yue-ping Ding; Ying Xu; Hong-Fei Liu (AAPS PharmSciTech, 2019)

Vanadium compounds induced damage of human umbilical vein endothelial cells and the protective effect of berberine - Cong-Cong Hou; Hong-Yu Liang; Yi-Hui Pan; Man Wang; Li-Li Zhao; Yuan Bian; Duan-Yuan Cao; Ding Zhao (BioMetals, 2019)

Eogenetic Karst in Interbedded Carbonates and Evaporites and Its Impact on Hydrocarbon Reservoir: A New Case from Middle Triassic Leikoupo Formation in Sichuan Basin, Southwest China - Hong Liu; Xiucheng Tan; Ling Li; Xiong Ding; Jian Cao; Guang Yang; Teng Ma (Journal of Earth Science, 2019)

Protective effect of isoliquiritigenin against cerebral injury in septic mice via attenuation of NF-κB - Peng Zou; Hong-Ming Ji; Jian-Wei Zhao; Xin-Min Ding; Zi-Gang Zhen; Xuan Zhang; Xiao-Qi Nie; Li-Xiong Xue (Inflammopharmacology, 2019)

Effects of NaCl stress on growth of Portulaca oleracea and underlying mechanisms - Jin-Cheng Xing; Jing Dong; Mao-Wen Wang; Chong Liu; Bao-Quan Zhao; Zhu-Gui Wen; Xiao-Mei Zhu; Hai-Rong Ding; Xiao-Hui Zhao; Li-Zhou Hong (Brazilian Journal of Botany, 2019)

BDNF-mediated mitophagy alleviates high-glucose-induced brain microvascular endothelial cell injury - Hong Jin; Yi Zhu; Yiping Li; Xiuyu Ding; Wenqi Ma; Xiqiong Han; Bilei Wang (Apoptosis, 2019)

Roles of hyaluronan in cardiovascular and nervous system disorders - Hong-yan Ding; Ya-nan Xie; Qiang Dong; Koji Kimata; Yoshihiro Nishida; Naoki Ishiguro; Li-sheng Zhuo (Journal of Zhejiang University-SCIENCE B, 2019)

Mechanism of Coordinate Anchorage Support of Bolt-Single Anchor Cable for Gob-Side Entry Roof - Hong-chao Li; Ke Ding; Qiang Xu; Qiang Zhang (Geotechnical and Geological Engineering, 2019)

Diltiazem used as a tacrolimus-sparing agent for treatment of pediatric patients with refractory nephrotic syndrome: a case report and retrospective analysis - Jie-Yu Sun; Ya-Hui Hu; Hong-Li Guo; Xia Jing; Ze-Jun Xu; Fang Sun; Hui-Lei Guo; Xuan-Sheng Ding; Feng Chen; Jing Xu (European Journal of Clinical Pharmacology, 2019)

Effects of chronic kidney disease stage 4, end-stage renal disease, or dialysis on the plasma concentrations of ombitasvir, paritaprevir, ritonavir, and dasabuvir in patients with chronic HCV infection: pharmacokinetic analysis of the phase 3 RUBY-I and RUBY-II trials - Diana L. Shuster; Rajeev M. Menon; Bifeng Ding; Amit Khatri; Hong Li; Eric Cohen; Melissa Jewett; Daniel E. Cohen; Jiuhong Zha (European Journal of Clinical Pharmacology, 2019)

High-sensitivity neuroimaging biomarkers for the identification of amnestic mild cognitive impairment based on resting-state fMRI and a triple network model - Enyan Yu; Zhengluan Liao; Yunfei Tan; Yaju Qiu; Junpeng Zhu; Zhang Han; Jue Wang; Xinwei Wang; Hong Wang; Yan Chen; Qi Zhang; Yumei Li; et al. (Brain Imaging and Behavior, 2019)

A novel long non-coding RNA, lncKBTBD10, involved in bovine skeletal muscle myogenesis - Mingming Chen; Xin Li; Xiaojuan Zhang; Yan Li; Junxing Zhang; Minhui Liu; Linlin Zhang; Xiangbin Ding; Xinfeng Liu; Hong Guo (In Vitro Cellular & Developmental Biology - Animal, 2019)

Mid–Late Cretaceous igneous activity in South China: the Qianjia example, Hainan Island - Sai-Jun Sun; Li-Peng Zhang; Rong-Qing Zhang; Xing Ding; Hong-Li Zhu; Zhao-Feng Zhang; Wei-Dong Sun (International Geology Review, 2018)

Three new 3,4-seco-cycloartane triterpenes from Gardenia sootepensis - Wei-Wu Song; Xue-Qin Wang; Hua-Li Jia; Zheng-Kun Zhang; Yong-Jie Ding; Ya-Hong Chen (Natural Product Research, 2018)

The relationship between putamen-SMA functional connectivity and sensorimotor abnormality in ESRD patients - Dun Ding; Peng Li; Xue-ying Ma; Wang-huan Dun; Shi-feng Yang; Shao-hui Ma; Hong-juan Liu; Ming Zhang (Brain Imaging and Behavior, 2018)

Two new polyols from cultures of the fungus Daedaleopsis tricolor - Jiang-Yuan Zhao; Jian-Hai Ding; Zheng-Hui Li; Tao Feng; Hong-Bin Zhang; Ji-Kai Liu (Natural Product Research, 2018)

A new cyclic dipeptide from cultures of Coprinus plicatilis - Jiang-Yuan Zhao; Jian-Hai Ding; Zheng-Hui Li; Tao Feng; Hong-Bin Zhang; Ji-Kai Liu (Natural Product Research, 2018)

Predictive modeling of microbial single cells: A review - Tian Ding; Xin-Yu Liao; Qing-Li Dong; Xiao-Ting Xuan; Shi-Guo Chen; Xing-Qian Ye; Dong-Hong Liu (Critical Reviews in Food Science and Nutrition, 2018)

Synthesis, biological evaluation, and molecular docking of ropivacaine analogs as local anesthetic agents - Wen Li; Lina Ding; Hong-Min Liu; Qidong You (Medicinal Chemistry Research, 2018)

Development and validation of SSR markers based on transcriptome sequencing of Casuarina equisetifolia - Nan Li; Yong-Qi Zheng; Hong-Mei Ding; He-Peng Li; Hua-Zheng Peng; Bo Jiang; Hai-Bo Li (Trees, 2018)

Effective removal of ammonia nitrogen from waste seawater using crystal seed enhanced struvite precipitation technology with response surface methodology for process optimization - Weilong Song; Zhipeng Li; Feng Liu; Yi Ding; Peishi Qi; Hong You; Chao Jin (Environmental Science and Pollution Research, 2018)

Comparative muscle proteomics/phosphoproteomics analysis provides new insight for the biosafety evaluation of fat-1 transgenic cattle - Xiangbo Xin; Xinfeng Liu; Xin Li; Xiangbin Ding; Shuping Yang; Congfei Jin; Guangpeng Li; Hong Guo (Transgenic Research, 2017)

Purinergic P2X7 receptor functional genetic polymorphisms are associated with the susceptibility to osteoporosis in Chinese postmenopausal women - Hong Xu; Chengxin Gong; Luling He; Shenqiang Rao; Xingzi Liu; Yijun Nie; Changle Liu; Tao Li; Lu Ding; Yunming Tu; Yuping Yang; Fangfang Hu; et al. (Purinergic Signalling, 2017)

Gene Polymorphisms for Both Auto-antigen and Immune-Modulating Proteins Are Associated with the Susceptibility of Autoimmune Myasthenia Gravis - Hai-Feng Li; Yu Hong; Xu Zhang; Yanchen Xie; Geir Olve Skeie; Hong-Jun Hao; Nils Erik Gilhus; Bing Liang; Yao-Xian Yue; Xian-Jun Zhang; Xiang Gao; Qi Wang; et al. (Molecular Neurobiology, 2017)

Isolation of Viable but Non-culturable Bacteria from Printing and Dyeing Wastewater Bioreactor Based on Resuscitation Promoting Factor - Yi Jin; Guojuan Gan; Xiaoyun Yu; Dongdong Wu; Li Zhang; Na Yang; Jiadan Hu; Zhiheng Liu; Lixin Zhang; Huachang Hong; Xiaoqing Yan; Yan Liang; et al. (Current Microbiology, 2017)

Work stress, family stress and asthma: a cross-sectional study among women in China - Adrian Loerbroks; Hui Ding; Wei Han; Hong Wang; Jiang-Ping Wu; Liu Yang; Peter Angerer; Jian Li (International Archives of Occupational and Environmental Health, 2017)

Temporal and spatial distributions of PBDEs in atmosphere at Shanghai rural regions, China - Yun-Juan Zhu; Dan Sun; Nuo-Er Yang; Yong-Sheng Ding; Wei-Bing Feng; Wen-Jun Hong; Shi-Mao Zhu; Yi-Fan Li (Environmental Science and Pollution Research, 2017)

Upper-ocean dynamical features and prediction of the super El Niño in 2015/16: A comparison with the cases in 1982/83 and 1997/98 - Hong-Li Ren; Run Wang; Panmao Zhai; Yihui Ding; Bo Lu (Journal of Meteorological Research, 2017)

Novel compound heterozygous mutations in ZAP70 in a Chinese patient with leaky severe combined immunodeficiency disorder - Qing Liu; Yan-Ping Wang; Qiao Liu; Qin Zhao; Xue-Mei Chen; Xiu-Hong Xue; Li-Na Zhou; Yuan Ding; Xue-Mei Tang; Xiao-Dong Zhao; Zhi-Yong Zhang (Immunogenetics, 2017)

A Comprehensive Meta-analysis of Genetic Associations Between Key Polymorphic Loci in DNA Repair Genes and Glioma Risk - Ling Qi; Hong-quan Yu; Yu Zhang; Li-juan Ding; Dong-hai Zhao; Peng Lv; Wei-yao Wang; Ye Xu (Molecular Neurobiology, 2017)

miR-143 regulates proliferation and differentiation of bovine skeletal muscle satellite cells by targeting IGFBP5 - Wei Ran Zhang; Hui Na Zhang; Yi Min Wang; Yang Dai; Xin Feng Liu; Xin Li; Xiang Bin Ding; Hong Guo (In Vitro Cellular & Developmental Biology - Animal, 2017)

Inhibition of the Receptor for Advanced Glycation End-Products (RAGE) Attenuates Neuroinflammation While Sensitizing Cortical Neurons Towards Death in Experimental Subarachnoid Hemorrhage - Hua Li; Jia-Sheng Yu; Ding-Ding Zhang; Yi-Qing Yang; Li-Tian Huang; Zhuang Yu; Ru-Dong Chen; Hong-Kuan Yang; Chun-Hua Hang (Molecular Neurobiology, 2017)

Identification of aberrant DNA methylation involved in chemoradiation-resistant HCT116 cells via methylation-specific microarray - Wei Xiong; Yun-Feng Li; Shan Liu; Ting Chen; Hong-Tao Zhang; Zhi-Bin Yang; Ying-Ying Ding; De-Pei Gao; Guan-Shun Wang; Jian Dong (Molecular & Cellular Toxicology, 2016)

Different effects of isolation-rearing and neonatal MK-801 treatment on attentional modulations of prepulse inhibition of startle in rats - Zhe-Meng Wu; Yu Ding; Hong-Xiao Jia; Liang Li (Psychopharmacology, 2016)

Seroprevalence and risk factors of severe fever with thrombocytopenia syndrome virus infection in endemic areas - Yong Lyu; Fan Ding; Jie Sun; Peng-Peng Xu; Jie-Ying Hu; Shao-Yu Xie; Kai-Chun Li; Hong-Wei Chang; Wei Qin; Liang Yu; Hua Xie; Guang-Jiang Li; et al. (Infectious Diseases, 2016)

Alterations and correlations of the gut microbiome, metabolism and immunity in patients with primary biliary cirrhosis - Long‐Xian Lv; Dai‐Qiong Fang; Ding Shi; De‐Ying Chen; Ren Yan; Yi‐Xin Zhu; Yan‐Fei Chen; Li Shao; Fei‐Fei Guo; Wen‐Rui Wu; Ang Li; Hai‐Yan Shi; et al. (Environmental Microbiology, 2016)
Summary We selected 42 early‐stage primary biliary cirrhosis (PBC) patients and 30 healthy controls (HC). Metagenomic sequencing of the 16S rRNA gene was used to characterize the fecal microbiome. UPLC‐MS/MS assaying of small molecules was used to characterize the metabolomes of the serum, urine and feces. Liquid chip assaying of serum cytokines was used to characterize the immune profiles. The gut of PBC patients were depleted of some potentially beneficial bacteria, such as Acidobacteria, Lachnobacterium sp., Bacteroides eggerthii and Ruminococcus bromii , but were enriched in some bacterial taxa containing opportunistic pathogens, such as γ‐Proteobacteria, Enterobacteriaceae, Neisseriaceae, Spirochaetaceae , Veillonella , Streptococcus , Klebsiella , Actinobacillus pleuropneumoniae , Anaeroglobus geminatus , Enterobacter asburiae , Haemophilus parainfluenzae , Megasphaera micronuciformis and Paraprevotella clara . Several altered gut bacterial taxa exhibited potential interactions with PBC through their associations with altered metabolism, immunity and liver function indicators, such as those of Klebsiella with IL‐2A and Neisseriaceae with urinary indoleacrylate. Many gut bacteria, such as some members of Bacteroides, were altered in their associations with the immunity and metabolism of PBC patients, although their relative abundances were unchanged. Consequently, the gut microbiome is altered and may be critical for the onset or development of PBC by interacting with metabolism and immunity.

LncRNA NONRATT021972 siRNA attenuates P2X7 receptor expression and inflammatory cytokine production induced by combined high glucose and free fatty acids in PC12 cells - Hong Xu; Luling He; Changle Liu; Lan Tang; Yonghu Xu; Mengqi Xiong; Mei Yang; Yongfang Fan; Fangfang Hu; Xingzi Liu; Lu Ding; Yun Gao; et al. (Purinergic Signalling, 2016)

MpMYBS3 as a crucial transcription factor of cold signaling confers the cold tolerance of banana - Tong-xin Dou; Chun-hua Hu; Xiao-xuan Sun; Xiu-hong Shao; Jun-hua Wu; Li-jie Ding; Jie Gao; Wei-di He; Manosh-Kumar Biswas; Qiao-song Yang; Gan-jun Yi (Plant Cell, Tissue and Organ Culture (PCTOC), 2016)

Factors Associated with Thrombolysis Outcome in Ischemic Stroke Patients with Atrial Fibrillation - Qiuyun Zhao; Xiaobo Li; Wanli Dong; Min Ye; Yongjun Cao; Meijuan Zhang; Qiantao Cheng; Junshan Zhou; Guofang Chen; Ming Yu; Shanshan Hong; Xiue Wei; et al. (Neuroscience Bulletin, 2016)

Oral administration of Anabaena-expressed VP28 for both drug and food against white spot syndrome virus in shrimp - Xiao-Hui Jia; Chun-Li Zhang; Ding-Ji Shi; Min-Min Zhuang; Xiang Wang; Rui Jia; Zheng-Yang Zhang; Jie Huang; Yi-Hua Sun; Wen-Yi Qian; Guo-Hong Peng; Pei-Min He (Journal of Applied Phycology, 2016)

Phylogenetic analysis of Leymus (Poaceae: Triticeae) based on Random Amplified Polymorphic DNA - Yang-Yi Li; Ying-Xia Lei; Guan-Hui Chai; Gang Gao; Jia-Bin Deng; Yan Zhang; Shan-Shan Tong; Chun-Bang Ding; Li Zhang; Yong-Hong Zhou; Rui-Wu Yang (Biologia, 2016)

CRMP1 Interacted with Spy1 During the Collapse of Growth Cones Induced by Sema3A and Acted on Regeneration After Sciatic Nerve Crush - Li Yao; Yong-hua Liu; Xiaohong Li; Yu-hong Ji; Xiao-jing Yang; Xian-ting Hang; Zong-mei Ding; Fang Liu; You-hua Wang; Ai-guo Shen (Molecular Neurobiology, 2016)

microRNA-128 regulates the proliferation and differentiation of bovine skeletal muscle satellite cells by repressing Sp1 - Yang Dai; Wei Ran Zhang; Yi Min Wang; Xin Feng Liu; Xin Li; Xiang Bin Ding; Hong Guo (Molecular and Cellular Biochemistry, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Erratum to: Microsatellite records for volume 7, issue 4 - Rose Komugisha Basiita; J. Henrich Bruggemann; Nianhui Cai; Conchi Cáliz-Campal; Chen Chen; Jiawei Chen; L. Cizek; Pedro J. Cordero; Deborah A. Dawson; Yandong Ding; L. Drag; Anan Duan; et al. (Conservation Genetics Resources, 2016)

Phylogenetic relationships and Y genome origin in Kengyilia (Triticeae: Poaceae) based on single copy gene DMC1 - Gang Gao; Zi-lin Tang; Jia-bin Deng; Xue-mei Gou; Qian Wang; Yan Zhang; Chun-bang Ding; Li Zhang; Yong-hong Zhou; Rui-wu Yang (Biologia, 2016)

Sources and potential health risk of gas phase PAHs in Hexi Corridor, Northwest China - Xiaoxuan Mao; Zhousuo Yu; Zhongyuan Ding; Tao Huang; Jianmin Ma; Gan Zhang; Jun Li; Hong Gao (Environmental Science and Pollution Research, 2016)

Ground deformation monitoring of Zhengzhou city from 2012 to 2013 using an improved IPTA - Hong-lei Yang; Jun-huan Peng; Bao-cun Wang; Yong-ze Song; Ding-xuan Zhang; Lihua Li (Natural Hazards, 2016)

The role of microRNA-1 and microRNA-206 in the proliferation and differentiation of bovine skeletal muscle satellite cells - Yang Dai; Yi Min Wang; Wei Ran Zhang; Xin Feng Liu; Xin Li; Xiang Bin Ding; Hong Guo (In Vitro Cellular & Developmental Biology - Animal, 2016)

The fate of urea nitrogen applied to a vegetable crop rotation system - Hong Ding; Shiqing Li; Yushu Zhang; Xiaoxia Hu; Xiangzhou Zheng; Jing Zhang; Boqi Weng; Deli Chen (Nutrient Cycling in Agroecosystems, 2015)

HPLC simultaneous determination of arbutin, chlorogenic acid and 6′- O -caffeoylarbutin in different parts of Vaccinium dunalianum Wight - Xu-Lu Luo; Na Li; Min Xu; Hong-Tao Zhu; Peng He; Yong Ding; Ping Zhao; Ying-Jun Zhang (Natural Product Research, 2015)

Physiological response to potassium deficiency in three sweet potato (Ipomoea batatas [L.] Lam.) genotypes differing in potassium utilization efficiency - Zhong-Hou Tang; Ai-Jun Zhang; Meng Wei; Xiao-Guang Chen; Zheng-Hui Liu; Hong-Min Li; Yan-Feng Ding (Acta Physiologiae Plantarum, 2015)

Porcine epidemic diarrhea virus uses cell-surface heparan sulfate as an attachment factor - Chang-chao Huan; Yue Wang; Bo Ni; Rui Wang; Li Huang; Xiao-feng Ren; Guang-zhi Tong; Chan Ding; Hong-jie Fan; Xiang Mao (Archives of Virology, 2015)

Flavobacterium shanxiense sp. nov., Isolated from Soil - Fan Yang; Hong-ming Liu; Rong Zhang; Ding-bin Chen; Xiang Wang; Xin Yan; Qing Hong; Shun-peng Li (Current Microbiology, 2015)

Screening for Fetal Spina Bifida Aperta by the Ultrasound and Intracranial Translucency Examinations at 11–13+6 Weeks of Gestation - Min Liu; Ying Liu; Zhi-hong Li; Ding Yu (Cell Biochemistry and Biophysics, 2015)

Diaphorobacter ruginosibacter sp. nov., isolated from soybean root nodule, and emended description of the genus Diaphorobacter - Xiu Li Wei; Meng Sha Han; Cong Cong Xia; Shu Lan Ding; Lin Xu; Yan Bing Lin; Li Wang; Ge Hong Wei (Archives of Microbiology, 2015)

The Therapeutic Potential of Rho Kinase Inhibitor Fasudil Derivative FaD-1 in Experimental Autoimmune Encephalomyelitis - Yong-Fei Zhao; Xiang Zhang; Zhi-Bin Ding; Xing-Wang Yang; Hui Zhang; Jie-Zhong Yu; Yan-Hua Li; Chun-Yun Liu; Qing Zhang; Hong-Zhen Zhang; Cun-Gen Ma; Bao-Guo Xiao (Journal of Molecular Neuroscience, 2015)

Optimized Preparation of a 99mTc-Radiolabeled Probe for Tracing MicroRNA - Lei Kang; Xiao-jie Xu; Chao Ma; Rong-fu Wang; Ping Yan; Chun-li Zhang; Hong-wei Sun; Ding Li (Cell Biochemistry and Biophysics, 2015)

Effects of continuous passage on immunomodulatory properties of human adipose-derived stem cells - Xiyou Wang; Cuilong Liu; Shaodan Li; Yong Xu; Ping Chen; Yi Liu; Qiang Ding; Wasilijiang Wahapu; Baofa Hong; Minghui Yang (Cell and Tissue Banking, 2015)

Mesenchymal stem cells alleviate atherosclerosis by elevating number and function of CD4+CD25+FOXP3+ regulatory T-cells and inhibiting macrophage foam cell formation - Zhi Xiao Wang; Chong Quan Wang; Xiao Yan Li; Gao Ke Feng; Hong Ling Zhu; Yan Ding; Xue Jun Jiang (Molecular and Cellular Biochemistry, 2015)

Effects of fructooligosaccharide on immune response, antioxidant capability and HSP70 and HSP90 expressions of blunt snout bream (Megalobrama amblycephala) under high ammonia stress - Chun-Nuan Zhang; Xiang-Fei Li; Hong-Yan Tian; Ding-Dong Zhang; Guang-Zhen Jiang; Kang-Le Lu; Guang-Xia Liu; Wen-Bin Liu (Fish Physiology and Biochemistry, 2015)

Phylogenetic relationships among Elymus and related diploid genera (Triticeae: Poaceae) based on nuclear rDNA ITS sequences - Gang Gao; Jia-bin Deng; Xue-mei Gou; Qian Wang; Chun-bang Ding; Li Zhang; Yong-hong Zhou; Rui-wu Yang (Biologia, 2015)

Comparative transcriptome analysis of RNA-seq data for cold-tolerant and cold-sensitive rice genotypes under cold stress - Chunxiu Shen; Ding Li; Ronghua He; Zhen Fang; Yumei Xia; Jing Gao; Hong Shen; Mengliang Cao (Journal of Plant Biology, 2014)

Allelopathic activity and chemical constituents of walnut ( Juglans regia ) leaf litter in walnut–winter vegetable agroforestry system - Qian Wang; Zheng Xu; Tingxing Hu; Hafeez ur Rehman; Hong Chen; Zhongbin Li; Bo Ding; Hongling Hu (Natural Product Research, 2014)

Retraction Note to: Characterization of cancer stem-like cells in the side population cells of human gastric cancer cell line MKN-45 - Hai-hong Zhang; Ai-zhen Cai; Xue-ming Wei; Li Ding; Feng-zhi Li; Ai-ming Zheng; Da-jiang Dai; Rong-rong Huang; Hou-jun Cao; Hai-yang Zhou; Jian-mei Wang; Xue-jing Wang; et al. (Journal of Zhejiang University-SCIENCE B, 2014)

Rooting characteristics of two widely distributed woody plant species growing in different karst habitats of southwest China - Yun-peng Nie; Hong-song Chen; Ke-lin Wang; Ya-li Ding (Plant Ecology, 2014)

Screening for Differentially Expressed Genes in Endophytic Fungus Strain 39 During Co-culture with Herbal Extract of its Host Dioscorea nipponica Makino - Chang-Hong Ding; Xiao-Wei Du; Ying Xu; Xiao-Meng Xu; Jin-Chao Mou; Dan Yu; Jun-Kai Wu; Fan-Jia Meng; Yan Liu; Wan-Li Wang; Li-Juan Wang (Current Microbiology, 2014)

Seasonal variations in leaf δ13C values: implications for different water-use strategies among species growing on continuous dolomite outcrops in subtropical China - Yun-peng Nie; Hong-song Chen; Ke-lin Wang; Ya-li Ding (Acta Physiologiae Plantarum, 2014)

Phylogenetic relationships between Leymus and related diploid Triticeae species revealed by ISSR markers - Guo-Ye Guo; Rui-Wu Yang; Chun-Bang Ding; Li Zhang; Yong-Hong Zhou; Fang Chen; Sheng-Hua Wang (Biologia, 2014)

Comparative proteome analysis of the response of ramie under N, P and K deficiency - Gang Deng; Li Jun Liu; Xin Yue Zhong; Cheng Ying Lao; Hong Yang Wang; Bo Wang; Cong Zhu; Fahad Shah; Ding Xiang Peng (Planta, 2014)

Assessing spatial distribution, sources, and human health risk of organochlorine pesticide residues in the soils of arid and semiarid areas of northwest China - Tao Huang; Qiang Guo; Hui Tian; Xiaoxuan Mao; Zhongyuan Ding; Gan Zhang; Jun Li; Jianmin Ma; Hong Gao (Environmental Science and Pollution Research, 2014)

Analysis of the Gut Microbiota by High-Throughput Sequencing of the V5–V6 Regions of the 16S rRNA Gene in Donkey - Xinfeng Liu; Hanlu Fan; Xiangbin Ding; Zhongshan Hong; Yongwei Nei; Zhongwei Liu; Guangpeng Li; Hong Guo (Current Microbiology, 2014)

Eukaryotic microbial communities in hypersaline soils and sediments from the alkaline hypersaline Huama Lake as revealed by 454 pyrosequencing - Kaihui Liu; Xiaowei Ding; Hong-Fei Wang; Xiaomei Zhang; Wael N. Hozzein; Mohammed A. M. Wadaan; Afeng Lan; Bo Zhang; Wenjun Li (Antonie van Leeuwenhoek, 2014)

MiR-200a is involved in proliferation and apoptosis in the human endometrial adenocarcinoma cell line HEC-1B by targeting the tumor suppressor PTEN - Rong Li; Jun-lin He; Xue-mei Chen; Chun-Lan Long; De-Hui Yang; Yu-Bin Ding; Hong-Bo Qi; Xue-Qing Liu (Molecular Biology Reports, 2014)

Epigallocatechin-3-gallate induces apoptosis, inhibits proliferation and decreases invasion of glioma cell - Hong Li; Zhe Li; Ya-Ming Xu; Yue Wu; Kang-Kang Yu; Can Zhang; Yong-Hua Ji; Gang Ding; Fu-Xue Chen (Neuroscience Bulletin, 2014)

Association of functional polymorphisms in the MxA gene with susceptibility to enterovirus 71 infection - Xiaoai Zhang; Hongmei Xu; Xiaodan Chen; Xiujun Li; Xianjun Wang; Shujun Ding; Renli Zhang; Lijuan Liu; Cui He; Lu Zhuang; Hao Li; Panhe Zhang; et al. (Human Genetics, 2014)

Effects of intercropping with Atractylodes lancea and application of bio-organic fertiliser on soil invertebrates, disease control and peanut productivity in continuous peanut cropping field in subtropical China - Xiao-gang Li; Xing-xiang Wang; Chuan-chao Dai; Tao-lin Zhang; Xing-guang Xie; Chang-feng Ding; Hong-wei Wang (Agroforestry Systems, 2014)

Construction and Characterization of a CTLA-4-Targeted scFv–Melittin Fusion Protein as a Potential Immunosuppressive Agent for Organ Transplant - Hailong Jin; Congran Li; Ding Li; Ming Cai; Zhouli Li; Shuang Wang; Xin Hong; Bingyi Shi (Cell Biochemistry and Biophysics, 2013)

Nucleolar dominance and different genome behaviors in hybrids and allopolyploids - Xian-Hong Ge; Li Ding; Zai-Yun Li (Plant Cell Reports, 2013)

Conditional and unconditional QTL mapping of drought-tolerance-related traits of wheat seedling using two related RIL populations - HONG ZHANG; FA CUI; LIN WANG; JUN LI; ANMING DING; CHUNHUA ZHAO; YINGUANG BAO; QIUPING YANG; HONGGANG WANG (Journal of Genetics, 2013)

Disruption of the transcription factor RBP-J results in osteopenia attributable to attenuated osteoclast differentiation - Jing Ma; Ya-Li Liu; Yi-Yang Hu; Ya-Ning Wei; Xing-Cheng Zhao; Guang-Ying Dong; Hong-Yan Qin; Yin Ding; Hua Han (Molecular Biology Reports, 2013)

RETRACTED ARTICLE: Characterization of cancer stem-like cells in the side population cells of human gastric cancer cell line MKN-45 - Hai-hong Zhang; Ai-zhen Cai; Xue-ming Wei; Li Ding; Feng-zhi Li; Ai-ming Zheng; Da-jiang Dai; Rong-rong Huang; Hou-jun Cao; Hai-yang Zhou; Jian-mei Wang; Xue-jing Wang; et al. (Journal of Zhejiang University-SCIENCE B, 2013)

Curcumin Ameliorates the Neurodegenerative Pathology in A53T α-synuclein Cell Model of Parkinson’s Disease Through the Downregulation of mTOR/p70S6K Signaling and the Recovery of Macroautophagy - Tian-Fang Jiang; Ying-Jie Zhang; Hai-Yan Zhou; Hong-Mei Wang; Li-Peng Tian; Jun Liu; Jian-Qing Ding; Sheng-Di Chen (Journal of Neuroimmune Pharmacology, 2013)

Large-scale gold mineralization in eastern China induced by an Early Cretaceous clockwise change in Pacific plate motions - Weidong Sun; Shuang Li; Xiaoyong Yang; Mingxing Ling; Xing Ding; Liu'an Duan; Meizhen Zhan; Hong Zhang; Weiming Fan (International Geology Review, 2013)

Functions of rice NAC transcriptional factors, ONAC122 and ONAC131, in defense responses against Magnaporthe grisea - Lijun Sun; Huijuan Zhang; Dayong Li; Lei Huang; Yongbo Hong; Xin Shun Ding; Richard S. Nelson; Xueping Zhou; Fengming Song (Plant Molecular Biology, 2013)

Comparative transcriptome analysis of tobacco (Nicotiana tabacum) leaves to identify aroma compound-related genes expressed in different cultivated regions - Bo Lei; Xue-Hua Zhao; Kai Zhang; Jie Zhang; Wei Ren; Zhu Ren; Yi Chen; Hui-Na Zhao; Wen-Jie Pan; Wei Chen; Hong-Xun Li; Wen-Ya Deng; et al. (Molecular Biology Reports, 2013)

Co-detection in the pathogenesis of severe hand-foot-mouth disease - Li-Juan Liu; Hong-Mei Xu; Xiu-Jun Li; Jun Wang; Xian-Jun Wang; Shu-Jun Ding; Fang Tang; Jing Wang; Ying-Jie Zhang (Archives of Virology, 2012)

Determination and Dynamics of Ethylicin Residues in Cotton-Field Ecosystem - Zilei Chen; Hong Zhang; Ruiyan Ding; Wenzheng Wang; Wenbo Wang; Huidong Li (Bulletin of Environmental Contamination and Toxicology, 2012)

Molecular and cytological evidences for the natural wheatgrass hybrids occurrence and origin in west China - Jian Zeng; Xing Fan; Hai-Qin Zhang; Li-Na Sha; Hou-Yang Kang; Li Zhang; Rui-Wu Yang; Chun-Bang Ding; Yong-Hong Zhou (Genes & Genomics, 2012)

Pseudolaric acid B-driven phosphorylation of c-Jun impairs its role in stabilizing HIF-1alpha: a novel function-converter model - Bing Yu; Mei-Hong Li; Wei Wang; Ying-Qing Wang; Yi Jiang; Sheng-Ping Yang; Jian-Min Yue; Jian Ding; Ze-Hong Miao (Journal of Molecular Medicine, 2012)

Formation of the world's largest molybdenum metallogenic belt: a plate-tectonic perspective on the Qinling molybdenum deposits - Cong-Ying Li; Fang-Yue Wang; Xi-Luo Hao; Xing Ding; Hong Zhang; Ming-Xing Ling; Ji-Bin Zhou; Yi-Liang Li; Wei-Ming Fan; Wei-Dong Sun (International Geology Review, 2012)

A mutation in the rice chalcone isomerase gene causes the golden hull and internode 1 phenotype - Lilan Hong; Qian Qian; Ding Tang; Kejian Wang; Ming Li; Zhukuan Cheng (Planta, 2012)

A centrifuge simulated push–pull manoeuvre with subsequent reduced +Gz tolerance - Yan Xu; Bao-Hui Li; Li-Hui Zhang; Zhao Jin; Xiao-Yang Wei; Hong Wang; San-Yuan Wu; Hai-Xia Wang; Quan Wang; Gui-Ding Yan; Lue Deng; Xi-Chen Geng (European Journal of Applied Physiology, 2012)

Synthesis of 2-R1-2-(4-(2-fluoroethoxy)benzamido)acetate as potential PET imaging agents - Yong He; Jingli Xu; Hang Liu; Man Feng; Xiao Wang; Rui Ding; Chuanmin Qi; Yurong Chen; Fang Li; Zhao-Hui Zhu; Yong-Hong Dang; Ming Wang; et al. (Medicinal Chemistry Research, 2012)

Phylogeny and molecular evolution of the DMC1 gene within the StH genome species in Triticeae (Poaceae) - Xiao-Li Wang; Xing Fan; Jian Zeng; Li-Na Sha; Hai-Qin Zhang; Hou-Yang Kang; Rui-Wu Yang; Li Zhang; Chun-Bang Ding; Yong-Hong Zhou (Genes & Genomics, 2012)

Evaluation of suitable reference genes for quantitative RT-PCR during development and abiotic stress in Panonychus citri (McGregor) (Acari: Tetranychidae) - Jin-Zhi Niu; Wei Dou; Tian-Bo Ding; Li-Hong Yang; Guang-Mao Shen; Jin-Jun Wang (Molecular Biology Reports, 2012)

MicroRNA- 1 represses Cx43 expression in viral myocarditis - Hong-Fei Xu; Yu-Jie Ding; Yi-Wen Shen; Ai-Min Xue; Hong-Mei Xu; Cheng-Liang Luo; Bei-Xu Li; Yue-Lin Liu; Zi-Qin Zhao (Molecular and Cellular Biochemistry, 2012)

An ERP study on the processing of common fractions - Li Zhang; Ziqiang Xin; Fuhong Li; Qi Wang; Cody Ding; Hong Li (Experimental Brain Research, 2012)

Phylogenetic relationships between Leymus (Poaceae, Triticeae) and related diploid Triticeae species based on isozyme and genome-specific random amplified polymorphic DNA (RAPD) markers - Rui-Wu Yang; Min-Han Zhong; Xue-Mei Zou; Chun-Bang Ding; Li Zhang; Yong-Hong Zhou (Plant Biosystems, 2012)

QTL detection of seven quality traits in wheat using two related recombinant inbred line populations - Jun Li; Fa Cui; An-ming Ding; Chun-hua Zhao; Xiu-qin Wang; Lin Wang; Yin-guang Bao; Xiao-lei Qi; Xing-feng Li; Ju-rong Gao; De-shun Feng; Hong-gang Wang (Euphytica, 2012)

Removal of genotoxicity in chlorinated secondary effluent of a domestic wastewater treatment plant during dechlorination - Qian-Yuan Wu; Yi Li; Hong-Ying Hu; Ya-Nan Ding; Huang Huang; Feng-Yun Zhao (Environmental Science and Pollution Research, 2012)

Forest Management in Northeast China: History, Problems, and Challenges - Dapao Yu; Li Zhou; Wangming Zhou; Hong Ding; Qingwei Wang; Yue Wang; Xiaoqing Wu; Limin Dai (Environmental Management, 2011)

General depositional features of the carbonate platform gas reservoir of the Lower Triassic Jialingjiang Formation in the Sichuan Basin of southwest China: Moxi gas field of the central basin - Xiucheng Tan; Ling Li; Hong Liu; Bing Luo; Yan Zhou; Jiajie Wu; Xiong Ding (Carbonates and Evaporites, 2011)

Genome-wide analysis of OCT4 binding sites in glioblastoma cancer cells - Xue-feng Fang; Wei-yi Zhang; Na Zhao; Wei Yu; Dong Ding; Xu Hong; Li-sha Li; Hua-rong Zhang; Shu Zheng; Biao-yang Lin (Journal of Zhejiang University-SCIENCE B, 2011)

Enhanced Gene Transduction into Skeletal Muscle of Mice In Vivo with Pluronic Block Copolymers and Ultrasound Exposure - Yun-Chao Chen; Li-Ping Jiang; Na-Xiang Liu; Lu Ding; Xiao-Ling Liu; Zhi-Hui Wang; Kai Hong; Qing-Ping Zhang (Cell Biochemistry and Biophysics, 2011)

Spatial and seasonal variation of polychlorinated biphenyls in Songhua River, China - Hong You; Jing Ding; Xue-Song Zhao; Yi-Fan Li; Li-Yan Liu; Wan-Li Ma; Hong Qi; Ji-Min Shen (Environmental Geochemistry and Health, 2011)

BRAF V600E mutation and resistance to anti-EGFR monoclonal antibodies in patients with metastatic colorectal cancer: a meta-analysis - Chen Mao; Ru-Yan Liao; Li-Xin Qiu; Xi-Wen Wang; Hong Ding; Qing Chen (Molecular Biology Reports, 2011)

Analysis of the Composition and Characteristics of Culturable Endophytic Bacteria Within Subnival Plants of the Tianshan Mountains, Northwestern China - Hong Mei Sheng; Hong Shan Gao; Lin Gui Xue; Shuo Ding; Chun Li Song; Hu Yuan Feng; Li Zhe An (Current Microbiology, 2011)

Geochemical and zircon U–Pb study of the Huangmeijian A-type granite: implications for geological evolution of the Lower Yangtze River belt - He Li; Hong Zhang; Ming-Xing Ling; Fang-Yue Wang; Xing Ding; Ji-Bin Zhou; Xiao-Yong Yang; Xiang-Lin Tu; Weidong Sun (International Geology Review, 2011)

Analysis of bacterial communities in rhizosphere soil of healthy and diseased cotton (Gossypium sp.) at different plant growth stages - Yan Zhang; Bing-Hai Du; Zhi-gang Jin; Zheng-hua Li; Hong-ning Song; Yan-Qin Ding (Plant and Soil, 2011)

Characterization of a wheat HSP70 gene and its expression in response to stripe rust infection and abiotic stresses - Ying-Hui Duan; Jun Guo; Ke Ding; Shu-Juan Wang; Hong Zhang; Xi-Wei Dai; Yue-Ying Chen; Francine Govers; Li-Li Huang; Zhen-Sheng Kang (Molecular Biology Reports, 2011)

Regulation of Root Growth in Lactuca sativa L. Seedlings by the Ent-Kaurane Diterpenoid Epinodosin - Lan Ding; Hong-Wei Jing; Tao Wang; Jing Li; Guo-An Liu (Journal of Plant Growth Regulation, 2010)

Photodynamic Therapy in the Treatment of Superficial Mycoses: An Evidence-based Evaluation - Jianjun Qiao; Ruoyu Li; Yingguo Ding; Hong Fang (Mycopathologia, 2010)

TGFBR1*6A/9A polymorphism and cancer risk: a meta-analysis of 13,662 cases and 14,147 controls - Ru-Yan Liao; Chen Mao; Li-Xin Qiu; Hong Ding; Qing Chen; Hai-Feng Pan (Molecular Biology Reports, 2010)

Structural basis for the decrease in the outward potassium channel current induced by lanthanum - Li Hong Wang; Na Jiang; Bo Zhao; Xiao Dong Li; Tian Hong Lu; Xiao Lan Ding; Xiao Hua Huang (JBIC Journal of Biological Inorganic Chemistry, 2010)

Ischemic compression block attenuates mechanical hyperalgesia evoked from latent myofascial trigger points - Yong-Hui Wang; Xin-Li Ding; Yang Zhang; Jing Chen; Hong-You Ge; Lars Arendt-Nielsen; Shou-Wei Yue (Experimental Brain Research, 2010)

Validation of Candidate Reference Genes for the Accurate Normalization of Real-Time Quantitative RT-PCR Data in Rice During Seed Development - Qian-Feng Li; Samuel S. M. Sun; Ding-Yang Yuan; Heng-Xiu Yu; Ming-Hong Gu; Qiao-Quan Liu (Plant Molecular Biology Reporter, 2010)

Potential role of the TLR4/IRAK-4 signaling pathway in the pathophysiology of acute pancreatitis in mice - Jun-Li Ding; Yuan Li; Xiang-Yu Zhou; Ling Wang; Bin Zhou; Rong Wang; Hong-Xiang Liu; Zong-Guang Zhou (Inflammation Research, 2009)

Valsartan preconditioning protects against myocardial ischemia–reperfusion injury through TLR4/NF-κB signaling pathway - Jian Yang; Hong Jiang; Jun Yang; Jia-Wang Ding; Li-Hua Chen; Song Li; Xiao-Dong Zhang (Molecular and Cellular Biochemistry, 2009)

The construction of siRNA plasmid targeting mouse HIF-1α and in vitro study of its inhibition effect - Zhen-Yu Ding; Ze-Gui Li; Yi-Zhan Xing; Hua Ji; Hong-Li Li; Zhi-Jie Chang (Neuroscience Bulletin, 2009)

Digenic inheritance of non-syndromic deafness caused by mutations at the gap junction proteins Cx26 and Cx31 - Xue-Zhong Liu; Yongyi Yuan; Denise Yan; Emilie Hong Ding; Xiao Mei Ouyang; Yu Fei; Wenxue Tang; Huijun Yuan; Qing Chang; Li Lin Du; Xin Zhang; Guojian Wang; et al. (Human Genetics, 2009)

Genome-wide association scan for stature in Chinese: evidence for ethnic specific loci - Shu-Feng Lei; Tie-Lin Yang; Li-Jun Tan; Xiang-Ding Chen; Yan Guo; Yan-Fang Guo; Liang Zhang; Xiao-Gang Liu; Han Yan; Feng Pan; Zhi-Xin Zhang; Yu-Mei Peng; et al. (Human Genetics, 2009)

Production and characterization of intergeneric somatic hybrids between Brassica napus and Orychophragmus violaceus and their backcrossing progenies - Zhi-gang Zhao; Ting-ting Hu; Xian-Hong Ge; Xue-zhu Du; Li Ding; Zai-yun Li (Plant Cell Reports, 2008)

Vesicular stomatitis virus matrix protein gene enhances the antitumor effects of radiation via induction of apoptosis - Xiao-Bo Du; Jin-Yi Lang; Jian-Rong XU; You Lu; Yan-Jun Wen; Ju-Mei Zhao; Peng Diao; Zhi-Ping Yuan; Bin Yao; Ling-Yu Fan; Guo-Qing Wang; Li Liu; et al. (Apoptosis, 2008)

Characterization of tomato zonate spot virus, a new tospovirus in China - Jia-Hong Dong; Xiao-Fei Cheng; Yue-Yan Yin; Qi Fang; Ming Ding; Ting-Ting Li; Li-Zhen Zhang; Xiao-Xia Su; Jenifer Huang McBeath; Zhong-Kai Zhang (Archives of Virology, 2008)

Sodium channel development and modulation of hypoxia and delta-opioid receptor on sodium channel expression in developing cortical neurons of rat brain - Hong Cao; Zhenhua Ding; Hua Zhong; Shuji Gong; Lidan Chen; Ming Li (Molecular and Cellular Biochemistry, 2008)

Screening and identification of vascular-endothelial-cell-specific binding peptide in gastric cancer - Shuhui Liang; Tao Lin; Jie Ding; Yanglin Pan; Dongmei Dang; Changcun Guo; Min Zhi; Pengtao Zhao; Li Sun; Liu Hong; Yongquan Shi; Liping Yao; et al. (Journal of Molecular Medicine, 2006)

Characterization of a cDNA coding for an extracellular calmodulin-binding protein from suspension-cultured cells of Angelica dahurica - Guo-Hong Mao; Li-Xia Hou; Cun-Bao Ding; Su-Juan Cui; Da-Ye Sun (Planta, 2005)

pp5644 Interacts with phosphatidylinositol-4-phosphate adaptor protein-1 associated protein-1 - Xiao-Xia Ye; Hong Lu; Yao Yu; Ning Ding; Nai-Ling Zhang; Ke-Ke Huo; Da-Fang Wan; Yu-Yang Li; Jian-Ren Gu (Molecular and Cellular Biochemistry, 2005)